Novel positive pole piece, battery and electric device

CN119731801AActive Publication Date: 2025-03-28CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380061331.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-04-13
Publication Date
2025-03-28
Estimated Expiration
2043-04-13

AI Technical Summary

Technical Problem

Existing secondary batteries using lithium iron manganese phosphate as the cathode active material have deficiencies in energy density, rate performance, kinetic performance, cycle life and safety, and cannot meet the high requirements of power batteries.

Method used

A new type of cathode plate is used, by doping element A at the manganese position and doping element R at the phosphorus position of lithium manganese phosphate, forming the first positive electrode active material with a core-shell structure, and mixing it with lithium manganese oxide to achieve The three-layer coating structure improves the stability and safety of the material.

Benefits of technology

The energy density, rate performance, cycle stability and safety performance of secondary batteries are significantly improved, the cycle life is extended, and the kinetic performance and low-temperature performance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731801A_ABST
    Figure CN119731801A_ABST
Patent Text Reader

Abstract

The invention provides a novel positive pole piece, a battery and an electric device. Wherein the positive pole piece comprises a first positive active material and a second positive active material; the first positive electrode active material comprises an inner core, a first coating layer coating the inner core, a second coating layer coating the first coating layer and a third coating layer coating the second coating layer; the core comprises a compound Li1 + xMn1-yAyP1-zRzO4, the first coating layer comprises crystalline pyrophosphate LiaMP2O7 and / or Mb (P2O7) c, the second coating layer comprises crystalline phosphate XnPO4, and the third coating layer comprises carbon; the second positive electrode active material contains lithium manganese oxide. The secondary battery prepared from the positive pole piece is high in energy density, high in rate capability, good in dynamic performance and low-temperature performance, good in cycle performance and high in safety.
Need to check novelty before this filing date? Find Prior Art

Description

A novel positive electrode sheet, battery and power-consuming device Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a novel positive electrode sheet, a battery, and an electrical device. Background Art

[0002] In recent years, the application of secondary batteries has become increasingly widespread. They are widely used in energy storage systems such as hydropower, thermal, wind, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. This tremendous development of secondary batteries has led to higher requirements for their energy density, cycle performance, and safety. While existing lithium iron manganese phosphate (LiMnFePO4) cathode active materials have their advantages, they can lead to reduced kinetic and rate performance, failing to meet the demands of power batteries.

[0003] Summary of the Invention

[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a new type of positive electrode plate, battery and electrical device to solve the technical problems of low energy density, low rate performance, poor kinetic performance, poor low temperature performance, short cycle life and low safety of batteries made of existing positive electrode active materials.

[0005] In order to achieve the above-mentioned object, the present application provides a first positive electrode sheet in a first aspect, comprising a first positive electrode active material and a second positive electrode active material;

[0006] The first positive electrode active material includes a core, a first coating layer covering the core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer; the core contains a compound Li 1+x Mn 1-y A y P 1-z R z O4, the first coating layer contains crystalline pyrophosphate Li a MP2O7 and / or M b (P2O7) c The second coating layer comprises crystalline phosphate X n PO4, the third coating layer comprises carbon;

[0007] in,

[0008] A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge;

[0009] The R includes one or more elements selected from B, Si, N and S;

[0010] The x is any value in the range of -0.100 to 0.100;

[0011] The y is any value within the range of 0.001 to 0.500;

[0012] The z is any value within the range of 0.001 to 0.100;

[0013] The crystalline pyrophosphate Li a MP2O7 and M b (P2O7) c Each of M independently comprises one or more elements selected from the group consisting of Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al.

[0014] Said a is any value in the range of 0 to 2;

[0015] b is any value in the range of 1 to 4;

[0016] Said c is any value in the range of 1 to 6;

[0017] The X includes one or more elements selected from the group consisting of Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al;

[0018] The n is greater than 0 and less than or equal to 3;

[0019] The second positive electrode active material includes lithium manganese oxide.

[0020] Therefore, the present application provides a new type of first positive electrode active material with a core-shell structure by doping element A at the manganese position of lithium manganese phosphate and doping element R at the phosphorus position to obtain a doped lithium manganese phosphate core and then performing three layers of coating on the surface of the core in sequence. The first positive electrode active material can significantly reduce manganese dissolution and reduce the lattice change rate. When used in secondary batteries, it can significantly improve the high-temperature cycle performance, cycle stability, high-temperature storage performance, rate performance, safety performance of the secondary battery and increase the capacity of the secondary battery.

[0021] The present application mixes a first positive electrode active material and a second positive electrode active material, lithium manganese oxide, so that particles of the first positive electrode active material are uniformly coated on the surface of the second positive electrode active material, so that the lattice of the second positive electrode active material is relatively independent and the skeleton is stable, and it is not easy to collapse during the charge and discharge process of the secondary battery, thereby further improving the cycle life of the secondary battery; and the coating layer formed by the first positive electrode active material provides elastic strain for external force impact or shear, effectively solving the safety problem of the second positive electrode active material. The advantages of the two materials complement each other, thereby improving the energy density of the secondary battery, and at the same time enabling the secondary battery to have excellent rate performance, dynamic performance, cycle performance, low temperature performance and safety.

[0022] Unless otherwise specified, in the above chemical formula, when A is two or more elements, the above-mentioned numerical ranges for y are not only defined for the stoichiometric number of each element serving as A, but also for the sum of the stoichiometric numbers of each element serving as A. For example, when A is two or more elements A1, A2, ...An, the stoichiometric numbers y1, y2, ...yn of A1, A2, ...An must each fall within the numerical range defined for y in this application, and the sum of y1, y2, ...yn must also fall within this numerical range. Similarly, for the case where R is two or more elements, the numerical ranges for the stoichiometric numbers of R defined in this application also have the above meanings.

[0023] Herein, the term "crystalline state" refers to a crystallinity of 50% or more, i.e., 50%-100%. Crystallinity of less than 50% is referred to as a glassy state. The crystalline pyrophosphate and crystalline phosphate of the present application have a crystallinity of 50% to 100%. Pyrophosphates and phosphates with a certain degree of crystallinity not only help to fully utilize the pyrophosphate coating layer's ability to hinder manganese dissolution and the phosphate coating layer's excellent ability to conduct lithium ions and reduce interfacial side reactions, but also enable the pyrophosphate coating layer and the phosphate coating layer to achieve better lattice matching, thereby achieving a close bond between the coating layers.

[0024] In any embodiment of the first aspect of the present application, the second positive electrode active material includes LiMn2O4.

[0025] Therefore, mixing the first positive electrode active material with the above-mentioned second positive electrode active material further improves the energy density and rate performance of the battery, improves the dynamic performance, low temperature performance and safety of the secondary battery, and extends the cycle life of the secondary battery.

[0026] In any embodiment of the first aspect of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector; the positive electrode film layer has a single-layer structure or a multi-layer structure; at least one of the positive electrode film layers with a single-layer structure includes the first positive electrode active material and the second positive electrode active material at the same time, and / or at least one layer of the at least one positive electrode film layer with a multi-layer structure includes the first positive electrode active material and the second positive electrode active material at the same time.

[0027] In any embodiment of the first aspect of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector; at least one of the positive electrode film layers has a multi-layer structure, and at least one of the positive electrode film layers with a multi-layer structure includes the first positive electrode active material and the second positive electrode active material in different layers respectively; optionally, at least one of the positive electrode film layers with a multi-layer structure includes the first positive electrode active material and the second positive electrode active material in adjacent layers respectively.

[0028] In any embodiment of the first aspect of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer A and a positive electrode film layer B respectively arranged on two surfaces of the positive electrode current collector; the positive electrode film layer A and the positive electrode film layer B each independently have a single-layer structure or a multi-layer structure; at least one layer of the positive electrode film layer A includes the first positive electrode active material, and at the same time, at least one layer of the positive electrode film layer B includes the second positive electrode active material.

[0029] Therefore, the present application improves the energy density of the secondary battery by mixing the first positive electrode active material and the second positive electrode active material, complementing the advantages of the two materials, while also enabling the secondary battery to have excellent rate performance, dynamic performance, cycle performance, low-temperature performance, and safety. The particles of the first positive electrode active material are evenly coated on the surface of the second positive electrode active material, making the lattice of the second positive electrode active material relatively independent and the skeleton stable, making it less likely to collapse during the charge and discharge process of the secondary battery, further improving the cycle life of the secondary battery; in addition, the coating formed by the first positive electrode active material provides elastic strain in the event of external impact or shear, effectively solving the safety problem of the second positive electrode active material.

[0030] In any embodiment of the first aspect of the present application, the mass ratio of the first positive electrode active material to the second positive electrode active material is 1:7 to 7:1, and can be optionally 1:4 to 4:1. This allows the secondary battery to have both excellent rate performance and cycle performance, high energy density, excellent kinetic performance, and low-temperature performance, while reducing interfacial side reactions and improving the safety of the secondary battery.

[0031] In any embodiment of the first aspect of the present application, in the first positive electrode active material, A comprises one or more elements selected from Fe, Ti, V, Ni, Co, and Mg. Selecting the doping element within the above-mentioned range is beneficial for enhancing the doping effect. On the one hand, this further reduces the lattice change rate, thereby suppressing manganese dissolution and reducing the consumption of electrolyte and active lithium. On the other hand, it is also beneficial for further reducing surface oxygen activity and reducing interfacial side reactions between the first positive electrode active material and the electrolyte, thereby improving the cycle performance and high-temperature storage performance of the secondary battery.

[0032] In any embodiment of the first aspect of the present application, in the first positive electrode active material, R includes one element selected from B, Si, N, and S. By selecting the doping element within the above range, the rate performance and electrical conductivity of the secondary battery can be further improved, thereby enhancing the specific capacity, cycle performance, and high-temperature performance of the secondary battery.

[0033] In any embodiment of the first aspect of the present application, in the first positive electrode active material, the ratio of y to 1-y is 1:10 to 1:1, and can be 1:4 to 1:1. This further improves the energy density, cycle performance, and rate performance of the secondary battery.

[0034] In any embodiment of the first aspect of the present application, in the first positive electrode active material, the ratio of z to 1-z is 1:9 to 1:999, and can be 1:499 to 1:249. This further improves the energy density, cycle performance, and rate performance of the secondary battery.

[0035] In any embodiment of the first aspect of the present application, in the first positive electrode active material, the interplanar spacing of the crystalline pyrophosphate in the first coating layer is in the range of 0.293-0.470 nm, and the angle range of the crystal direction (111) is 18.00°-32.00°; and / or, the interplanar spacing of the crystalline phosphate in the second coating layer is in the range of 0.244-0.425 nm, and the angle range of the crystal direction (111) is 20.00°-37.00°.

[0036] The first coating layer and the second coating layer of the first positive electrode active material of the present application are both crystalline materials, and their interplanar spacing and angle ranges are within the above-mentioned ranges. This effectively avoids impurity phases in the coating layers, thereby increasing the specific capacity of the material and improving the cycle performance and rate performance of the secondary battery.

[0037] In any embodiment of the first aspect of the present application, in the first positive electrode active material, the carbon in the third coating layer is a mixture of SP2 carbon and SP3 carbon. Optionally, the molar ratio of SP2 carbon to SP3 carbon is any value in the range of 0.1-10, and can be any value in the range of 2.0-3.0.

[0038] The present application improves the overall performance of the secondary battery by limiting the molar ratio of SP2 carbon to SP3 carbon within the above range.

[0039] In any embodiment of the first aspect of the present application, the coating amount of the first coating layer is greater than 0 and less than or equal to 6% by weight, optionally greater than 0 and less than or equal to 5.5% by weight, and more optionally greater than 0 and less than or equal to 2% by weight, based on the weight of the core; and / or,

[0040] The coating amount of the second coating layer is greater than 0 and less than or equal to 6% by weight, optionally greater than 0 and less than or equal to 5.5% by weight, and more optionally 2-4% by weight, based on the weight of the core; and / or,

[0041] The coating amount of the third coating layer is greater than 0 and less than or equal to 6 wt %, optionally greater than 0 and less than or equal to 5.5 wt %, and more optionally greater than 0 and less than or equal to 2 wt %, based on the weight of the core.

[0042] In the first positive electrode active material with a core-shell structure of the present application, the coating amount of the three coating layers is preferably within the above range, thereby being able to fully coat the inner core and at the same time further improve the kinetic performance and safety performance of the secondary battery without sacrificing the gram capacity of the first positive electrode active material.

[0043] In any embodiment of the first aspect of the present application, in the first positive electrode active material, the thickness of the first coating layer is 1-10 nm. In the present application, when the thickness of the first coating layer is in the range of 1-10 nm, it is beneficial to improve the kinetic performance of the battery and can effectively hinder the migration of transition metal ions.

[0044] In any embodiment of the first aspect of the present application, in the first positive electrode active material, the second coating layer has a thickness of 2-15 nm. When the thickness of the second coating layer is within the range of 2-15 nm, the surface structure of the second coating layer is stable and side reactions with the electrolyte are minimal, thereby effectively reducing interfacial side reactions and improving the high-temperature performance of the secondary battery.

[0045] In any embodiment of the first aspect of the present application, in the first positive electrode active material, the thickness of the third coating layer is 2-25 nm. When the thickness of the third coating layer is in the range of 2-25 nm, the electrical conductivity of the material can be improved and the compaction density of the battery electrode sheet prepared using the first positive electrode active material can be improved.

[0046] In any embodiment of the first aspect of the present application, in the first positive electrode active material, based on the weight of the first positive electrode active material, the manganese content is in the range of 10 weight%-35 weight%, optionally in the range of 15 weight%-30 weight%, and more optionally in the range of 17 weight%-20 weight%.

[0047] In the first positive electrode active material with a core-shell structure of the present application, the content of manganese element is within the above-mentioned range, which can effectively improve the structural stability and density of the material, thereby improving the cycle, storage and compaction density performance of the secondary battery; and can increase the voltage platform, thereby improving the energy density of the secondary battery.

[0048] In any embodiment of the first aspect of the present application, in the first positive electrode active material, the content of phosphorus is in the range of 12 wt %-25 wt %, optionally in the range of 15 wt %-20 wt %, based on the weight of the first positive electrode active material.

[0049] In the first positive electrode active material with a core-shell structure of the present application, the content of phosphorus element is within the above-mentioned range, which can improve the electrical conductivity of the material, and at the same time can improve the stability of the pyrophosphate lattice structure in the inner core, the first coating layer and / or the phosphate in the second coating layer, thereby improving the overall stability of the material.

[0050] In any embodiment of the first aspect of the present application, in the first positive electrode active material, based on the weight of the first positive electrode active material, the weight ratio of manganese element to phosphorus element is 0.90-1.25, and can be optionally 0.95-1.20.

[0051] In the first positive electrode active material with a core-shell structure of the present application, the weight ratio of manganese element to phosphorus element is within the above-mentioned range, which can effectively inhibit the dissolution of transition metals, improve the stability of the material and the cycle and storage performance of the secondary battery; at the same time, it increases the discharge voltage platform of the material, thereby increasing the energy density of the secondary battery.

[0052] In any embodiment of the first aspect of the present application, the lattice change rate of the first positive electrode active material before and after complete lithium deintercalation is less than or equal to 4%, optionally less than or equal to 3.8%, and more optionally 2.0%-3.8%.

[0053] The core-shell structured first cathode active material of the present invention can achieve a lattice change rate of less than 4% before and after lithium insertion and extraction. Therefore, the use of the first cathode active material can improve the gram capacity and rate performance of the secondary battery.

[0054] In any embodiment of the first aspect of the present application, the Li / Mn antisite defect concentration of the first positive electrode active material is less than or equal to 4%, optionally less than or equal to 2.2%, and more optionally 1.5%-2.2%. By keeping the Li / Mn antisite defect concentration within the above range, the Mn 2+ Obstacle Li + transmission, while improving the gram capacity of the first positive electrode active material and the rate performance of the secondary battery.

[0055] In any embodiment of the first aspect of the present application, the compaction density of the first positive electrode active material at 3T is greater than or equal to 2.2 g / cm 3 , can be selected as greater than or equal to 2.2g / cm 3 and less than or equal to 2.8g / cm 3 Thus, by increasing the compaction density, the weight of the first positive electrode active material per unit volume increases, which is beneficial to improving the volume energy density of the secondary battery.

[0056] In any embodiment of the first aspect of the present application, the surface oxygen valence state of the first positive electrode active material is less than or equal to -1.90, and can optionally be between -1.98 and -1.90. Thus, by limiting the surface oxygen valence state of the first positive electrode active material to the above range, it is possible to reduce interfacial side reactions between the first positive electrode material and the electrolyte, thereby improving the battery cell's cycling performance, high-temperature storage gas production, and other performance.

[0057] In any embodiment of the first aspect of the present application, the sum of the mass of the first positive electrode active material and the second positive electrode active material accounts for 88% to 98.7% of the mass of the positive electrode sheet, further ensuring that the secondary battery has excellent rate performance, kinetic performance, cycle performance, and low-temperature performance, and has a high energy density.

[0058] The second aspect of the present application provides a battery, comprising the positive electrode sheet of the first aspect of the present application.

[0059] A third aspect of the present application provides an electrical device comprising the battery of the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] FIG1 is a schematic diagram of a first positive electrode active material having a three-layer coating structure according to an embodiment of the present application.

[0061] FIG. 2 is a schematic diagram of a secondary battery according to an embodiment of the present application.

[0062] FIG. 3 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 2 .

[0063] FIG4 is a schematic diagram of a battery module according to an embodiment of the present application.

[0064] FIG5 is a schematic diagram of a battery pack according to an embodiment of the present application.

[0065] FIG. 6 is an exploded view of the battery pack shown in FIG. 5 according to an embodiment of the present application.

[0066] FIG. 7 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.

[0067] FIG8 is a schematic diagram of a battery structure made of the positive electrode sheet P1 of the present application.

[0068] FIG9 is a schematic diagram of a battery structure made of the positive electrode sheet P2 of the present application.

[0069] FIG10 is a schematic diagram of a battery structure made of the positive electrode sheet P3 of the present application.

[0070] FIG11 is a schematic diagram of a battery structure made of the positive electrode sheet P8 of the present application.

[0071] FIG12 is a schematic diagram of a battery structure made of the positive electrode sheet P10 of the present application.

[0072] FIG13 is a schematic diagram of a battery structure made of the positive electrode sheet P11 of the present application.

[0073] FIG14 is a schematic diagram of a battery structure made of the positive electrode sheet P12 of the present application.

[0074] FIG15 is a schematic diagram of a battery structure made of the positive electrode sheet P17 of the present application.

[0075] FIG16 is a schematic diagram of a battery structure made of the positive electrode sheet P18 of the present application.

[0076] FIG17 is a schematic diagram of a battery structure made of the positive electrode sheet P23 of the present application.

[0077] FIG18 is a schematic diagram of a battery structure made of the positive electrode sheet P24 of the present application.

[0078] FIG19 is a schematic diagram of a battery structure made of the positive electrode sheet P26 of the present application.

[0079] FIG20 is a schematic diagram of a battery structure made of the positive electrode sheet P27 of the present application.

[0080] Explanation of reference numerals: 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 secondary battery; 51 housing; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0081] Below, the embodiments of the positive electrode sheet, secondary battery, battery module, battery pack and electric device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0082] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0083] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0084] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0085] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may further include step (c), which indicates that step (c) may be added to the method in any order, for example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.

[0086] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may indicate that other components not listed may also be included or that only the listed components are included.

[0087] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A and / or B" means "A, B, or both A and B." More specifically, the condition "A and / or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0088] If not otherwise specified, in this application, the term "at least one" refers to one or more, such as one, two, etc.

[0089] If there is no special explanation, in this application, the median particle size Dv 50 Refers to the particle size corresponding to the cumulative volume distribution percentage of the positive electrode active material reaching 50%. In this application, the median particle size Dv of the positive electrode active material is 50 Laser diffraction particle size analysis can be used for determination, for example, referring to the standard GB / T 19077-2016, using a laser particle size analyzer (such as Malvern Master Size 3000).

[0090] Unless otherwise specified, in this application, the term "coating" refers to a material layer coating the inner core. The material layer may completely or partially coat the inner core. The term "coating" is used for ease of description only and is not intended to limit the present invention. Similarly, the term "thickness of the coating" refers to the thickness of the material layer coating the inner core in the radial direction of the inner core.

[0091] Unless otherwise specified, in this application, the term "source" refers to a compound that is the source of a certain element. As examples, types of "source" include but are not limited to carbonates, sulfates, nitrates, elements, halides, oxides and hydroxides, etc.

[0092] [Secondary battery]

[0093] Secondary batteries, also known as rechargeable batteries or storage batteries, are batteries that can be recharged to activate the active materials after discharge and continue to be used.

[0094] Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. During the battery's charge and discharge process, active ions (such as lithium ions) are embedded and released back and forth between the positive and negative electrode sheets. The separator is set between the positive and negative electrode sheets, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing active ions to pass through. The electrolyte between the positive and negative electrode sheets mainly plays the role of conducting active ions.

[0095] [Positive electrode]

[0096] The present application provides a positive electrode sheet, comprising a first positive electrode active material and a second positive electrode active material;

[0097] The first positive electrode active material includes a core, a first coating layer covering the core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer; the core contains a compound Li 1+x Mn 1-y A y P 1-z R z O4, the first coating layer contains crystalline pyrophosphate Li a MP2O7 and / or M b (P2O7) c The second coating layer comprises crystalline phosphate X n PO4, the third coating layer comprises carbon;

[0098] in,

[0099] A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge;

[0100] The R includes one or more elements selected from B, Si, N and S;

[0101] The x is any value in the range of -0.100 to 0.100;

[0102] The y is any value within the range of 0.001 to 0.500;

[0103] The z is any value within the range of 0.001 to 0.100;

[0104] The crystalline pyrophosphate Li a MP2O7 and M b (P2O7) c Each of M independently comprises one or more elements selected from the group consisting of Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al.

[0105] Said a is any value in the range of 0 to 2;

[0106] b is any value in the range of 1 to 4;

[0107] Said c is any value in the range of 1 to 6;

[0108] The X includes one or more elements selected from the group consisting of Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al;

[0109] The n is greater than 0 and less than or equal to 3;

[0110] The second positive electrode active material includes lithium manganese oxide.

[0111] The first positive electrode active material of the present application can improve the gram capacity, cycle performance and safety performance of the secondary battery. Although the mechanism is not clear, it is speculated that the first positive electrode active material of the present application is a core-shell structure, wherein by doping the manganese site and phosphorus site of the lithium manganese phosphate core with element A and element R respectively, it can not only effectively reduce manganese dissolution, thereby reducing the manganese ions migrating to the negative electrode, reducing the electrolyte consumed due to the decomposition of the SEI film, and improving the cycle performance and safety performance of the secondary battery, but also promote the adjustment of the Mn-O bond, reduce the lithium ion migration barrier, promote lithium ion migration, and improve the rate performance of the secondary battery; by coating the core with a first coating layer including crystalline pyrophosphate, it can further The first cathode material is further coated with a crystalline phosphate coating layer with excellent lithium ion conductivity, which effectively reduces the surface interfacial side reactions on the surface of the first cathode active material, thereby improving the high-temperature cycling and storage performance of the secondary battery. The second cathode material is further coated with a carbon layer as a third coating layer, which further enhances the safety and kinetic performance of the secondary battery. In addition, the addition of element A to the manganese position of the lithium manganese phosphate in the core also helps reduce the lattice change rate of the lithium manganese phosphate during the lithium insertion and extraction process, thereby improving the structural stability of the first cathode material, significantly reducing manganese dissolution, and reducing oxygen activity on the particle surface. The addition of element R to the phosphorus position also helps change the ease of change in the Mn-O bond length, thereby improving electronic conductivity and reducing the lithium ion migration barrier, promoting lithium ion migration, and improving the rate performance of the secondary battery.

[0112] The present application mixes a first positive electrode active material and a second positive electrode active material, lithium manganese oxide, so that particles of the first positive electrode active material are uniformly coated on the surface of the second positive electrode active material, so that the lattice of the second positive electrode active material is relatively independent and the skeleton is stable, and it is not easy to collapse during the charge and discharge process of the secondary battery, thereby further improving the cycle life of the secondary battery; and the coating layer formed by the first positive electrode active material provides elastic strain for external force impact or shear, effectively solving the safety problem of the second positive electrode active material. The advantages of the two materials complement each other, thereby improving the energy density of the secondary battery, and at the same time enabling the secondary battery to have excellent rate performance, dynamic performance, cycle performance, low temperature performance and safety.

[0113] Unless otherwise specified, in the above chemical formula, when A is two or more elements, the above-mentioned numerical ranges for y are not only defined for the stoichiometric number of each element serving as A, but also for the sum of the stoichiometric numbers of each element serving as A. For example, when A is two or more elements A1, A2, ...An, the stoichiometric numbers y1, y2, ...yn of A1, A2, ...An must each fall within the numerical range defined for y in this application, and the sum of y1, y2, ...yn must also fall within this numerical range. Similarly, for the case where R is two or more elements, the numerical ranges for the stoichiometric numbers of R defined in this application also have the above meanings.

[0114] In some embodiments, the second positive electrode active material includes LiMn2O4.

[0115] Therefore, mixing the first positive electrode active material with the above-mentioned second positive electrode active material further improves the energy density and rate performance of the battery, improves the dynamic performance, low temperature performance and safety of the secondary battery, and extends the cycle life of the secondary battery.

[0116] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector; the positive electrode film layer has a single-layer structure or a multi-layer structure; at least one of the positive electrode film layers with a single-layer structure includes the first positive electrode active material and the second positive electrode active material at the same time, and / or at least one layer of at least one of the positive electrode film layers with a multi-layer structure includes the first positive electrode active material and the second positive electrode active material at the same time.

[0117] It should be noted that: when the positive electrode sheet includes two positive electrode film layers, "the positive electrode film layer has a single-layer structure or a multi-layer structure" means that the two positive electrode film layers independently have a single-layer structure or a multi-layer structure.

[0118] In some embodiments, a positive electrode film layer is respectively provided on the two surfaces of the positive electrode current collector, each positive electrode film layer is a single-layer structure, one positive electrode film layer includes both the first positive electrode active material and the second positive electrode active material, and the other positive electrode film layer includes the first positive electrode active material and / or the second positive electrode active material.

[0119] In some embodiments, a positive electrode film layer is respectively provided on both surfaces of the positive electrode current collector, each positive electrode film layer is a multi-layer structure, and at least one layer (for example, one layer) in each positive electrode film layer includes both the first positive electrode active material and the second positive electrode active material; optionally, the remaining layers in each positive electrode film layer include the first positive electrode active material or the second positive electrode active material.

[0120] In some embodiments, a positive electrode film layer C and a positive electrode film layer D are respectively provided on the two surfaces of the positive electrode current collector, the positive electrode film layer C is a multi-layer structure, and the positive electrode film layer D is a single-layer structure; at least one layer of the positive electrode film layer C includes the first positive electrode active material and the second positive electrode active material at the same time, and / or the positive electrode film layer D includes the first positive electrode active material and the second positive electrode active material at the same time; optionally, when any layer of the positive electrode film layer C and the positive electrode film layer D include the first positive electrode active material and the second positive electrode active material at the same time, the remaining layers of the positive electrode film layer C include the first positive electrode active material or the second positive electrode active material; optionally, when any layer of the positive electrode film layer C includes the first positive electrode active material and the second positive electrode active material at the same time, the remaining layers of the positive electrode film layer C and the positive electrode film layer D each independently include the first positive electrode active material or the second positive electrode active material; optionally, when the positive electrode film layer D includes the first positive electrode active material and the second positive electrode active material at the same time, each layer of the positive electrode film layer C each independently includes the first positive electrode active material or the second positive electrode active material.

[0121] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector; at least one of the positive electrode film layers has a multi-layer structure, and at least one of the positive electrode film layers with a multi-layer structure includes the first positive electrode active material and the second positive electrode active material in different layers respectively; optionally, at least one of the positive electrode film layers with a multi-layer structure includes the first positive electrode active material and the second positive electrode active material in adjacent layers respectively.

[0122] In some embodiments, a positive electrode film layer is provided on each surface of the positive electrode current collector, each positive electrode film layer is a multi-layer structure, and two adjacent layers in each positive electrode film layer include a first positive electrode active material and a second positive electrode active material, respectively.

[0123] In some embodiments of the present application, a positive electrode film layer E and a positive electrode film layer F are respectively provided on the two surfaces of the positive electrode current collector, the positive electrode film layer E is a multi-layer structure, the positive electrode film layer F is a single-layer structure, and the two adjacent layers in the positive electrode film layer E respectively include a first positive electrode active material and a second positive electrode active material; optionally, the remaining layers in the positive electrode film layer E and the positive electrode film layer F each independently include the first positive electrode active material or the second positive electrode active material.

[0124] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer A and a positive electrode film layer B respectively arranged on the two surfaces of the positive electrode current collector; the positive electrode film layer A and the positive electrode film layer B each independently have a single-layer structure or a multi-layer structure; at least one layer of the positive electrode film layer A includes the first positive electrode active material, and at the same time, at least one layer of the positive electrode film layer B includes the second positive electrode active material.

[0125] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer A and a positive electrode film layer B respectively arranged on two surfaces of the positive electrode current collector; the positive electrode film layer A and the positive electrode film layer B both have a single-layer structure; the positive electrode film layer A includes the first positive electrode active material, and at the same time, the positive electrode film layer B includes the second positive electrode active material.

[0126] This application utilizes a mixture of a first positive electrode active material and a second positive electrode active material, utilizing the complementary advantages of the two materials to enhance the energy density of the secondary battery while also providing the secondary battery with excellent rate performance, dynamic performance, cycle performance, low-temperature performance, and safety. The particles of the first positive electrode active material are uniformly coated on the surface of the second positive electrode active material, making the crystal lattice of the second positive electrode active material relatively independent and its skeleton stable, making it less prone to collapse during the charge and discharge process of the secondary battery, further enhancing the cycle life of the secondary battery. Furthermore, the coating formed by the first positive electrode active material provides elastic strain in the event of external impact or shear, effectively addressing the safety issues of the second positive electrode active material.

[0127] In some embodiments, when A includes one, two, three, or four elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge, A y Q n1 D n2 E n3 K n4 , where n1+n2+n3+n4=y, and n1, n2, n3, n4 are all positive numbers and not zero at the same time, Q, D, E, K are each independently selected from one of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and optionally, at least one of Q, D, E, K is Fe. Optionally, one of n1, n2, n3, n4 is zero, and the others are not zero; more optionally, two of n1, n2, n3, n4 are zero, and the others are not zero; further optionally, three of n1, n2, n3, n4 are zero, and the others are not zero. Kernel Li 1+x Mn 1-y A y P 1-z R z In O4, it is advantageous to dope one, two, three or four of the above-mentioned A elements at the manganese position, and optionally, one, two or three of the above-mentioned A elements; in addition, it is advantageous to dope one or two R elements at the phosphorus position, which is conducive to uniform distribution of the doping elements.

[0128] In some embodiments, the values ​​of x, y, and z are such that the entire core remains electrically neutral.

[0129] Kernel Li 1+x Mn 1-y A y P 1-z R z In O4, the size of x is affected by the valence of A and R, as well as the sizes of y and z, to ensure that the entire system is electrically neutral. If the value of x is too small, the lithium content of the entire core system will be reduced, affecting the specific capacity of the material. The value of y will limit the total amount of all doping elements. If y is too small, that is, the doping amount is too little, the doping element will not have any effect. If y exceeds 0.5, the Mn content in the system will be low, affecting the voltage platform of the material. The R element is doped in the position of P. Since the PO tetrahedron is relatively stable, and a too large z value will affect the stability of the material, the z value is limited to 0.001-0.100.

[0130] Furthermore, maintaining electrical neutrality throughout the core system minimizes defects and impurities in the first cathode active material. If the first cathode active material contains an excess transition metal (e.g., manganese), due to the inherently stable structure of the material system, the excess transition metal is likely to precipitate as a single element or form impurities within the crystal lattice. Maintaining electrical neutrality minimizes these impurities. Furthermore, ensuring the system's electrical neutrality can, in some cases, create lithium vacancies within the material, resulting in superior kinetic performance.

[0131] The values ​​of a, b, c and n satisfy the following conditions: a MP2O7 or M b (P2O7) c 、Crystalline Phosphate X n PO4 maintains electrical neutrality.

[0132] Crystalline means a crystallinity of 50% or more, i.e., 50%-100%. A crystallinity of less than 50% is called a glassy state. The crystalline pyrophosphate and crystalline phosphate of the present application have a crystallinity of 50% to 100%. Pyrophosphates and phosphates with a certain degree of crystallinity not only help to fully utilize the pyrophosphate coating layer's ability to hinder manganese dissolution and the phosphate coating layer's excellent ability to conduct lithium ions and reduce interfacial side reactions, but also enable better lattice matching between the pyrophosphate coating layer and the phosphate coating layer, thereby achieving a tighter bonding of the coating layers.

[0133] The crystallinity of the first coating layer material crystalline pyrophosphate and the second coating layer material crystalline phosphate of the first positive active material can be tested by conventional technical means in the art, such as density method, infrared spectroscopy, differential scanning calorimetry and nuclear magnetic resonance absorption method, and can also be tested by, for example, X-ray diffraction method.

[0134] A specific method for testing the crystallinity of the first coating layer crystalline pyrophosphate and the second coating layer crystalline phosphate of the first positive electrode active material by X-ray diffraction may include the following steps:

[0135] A certain amount of the first positive electrode active material powder is taken and the total scattering intensity is measured by X-rays. This is the sum of the scattering intensities of all matter in space and is only related to the intensity of the primary rays, the chemical structure of the first positive electrode active material powder, and the total number of electrons participating in the diffraction, i.e., the mass, but has nothing to do with the order state of the sample. The crystalline scattering and the non-crystalline scattering are then separated from the diffraction pattern. The degree of crystallinity is the ratio of the scattering intensity of the crystalline part to the total scattering intensity.

[0136] It should be noted that the crystallinity of the pyrophosphate and phosphate in the coating layer can be adjusted by, for example, adjusting the process conditions of the sintering process, such as the sintering temperature and the sintering time.

[0137] Because metal ions are difficult to migrate in pyrophosphate, pyrophosphate as the first coating layer effectively isolates the doped metal ions from the electrolyte. Crystalline pyrophosphate has a stable structure, so coating with crystalline pyrophosphate can effectively inhibit the dissolution of transition metals and improve cycling performance.

[0138] The bonding between the first coating layer and the core is similar to a heterojunction, and the strength of the bonding is limited by the degree of lattice matching. When the lattice mismatch is below 5%, the lattice matching is better, and the two are easy to bond tightly. Tight bonding can ensure that the coating will not fall off during subsequent cycles, which is beneficial to ensure the long-term stability of the material. The degree of bonding between the first coating layer and the core is measured mainly by calculating the mismatch between the lattice constants of the core and the coating. In the present application, after A and R elements are doped into the core, the matching degree between the core and the first coating layer is improved compared to undoped elements, and the core and the pyrophosphate coating layer can be more tightly bonded together.

[0139] The reason for choosing crystalline phosphate as the second coating layer is, firstly, because it has a high lattice match with the first coating layer, crystalline pyrophosphate (the mismatch is only 3%); secondly, the stability of phosphate itself is better than that of pyrophosphate, and using it to coat pyrophosphate is beneficial to improving the stability of the material. The structure of crystalline phosphate is very stable and it has excellent lithium ion conductivity. Therefore, using crystalline phosphate for coating can effectively reduce the interfacial side reactions on the surface of the first positive electrode active material, thereby improving the high-temperature cycle and storage performance of the secondary battery. The lattice matching between the second coating layer and the first coating layer is similar to the bonding between the first coating layer and the core mentioned above. When the lattice mismatch is less than 5%, the lattice matching is better and the two are easy to bond tightly.

[0140] The primary reason for using carbon as the third coating layer is its excellent electronic conductivity. Since electrochemical reactions occur in secondary batteries, which require the participation of electrons, carbon coating with excellent conductivity is used to enhance electron transfer between particles and between different locations on the particle. Carbon coating effectively improves the conductivity and desolvation capacity of the first cathode active material.

[0141] Figure 1 is a schematic diagram of an ideal three-layer coating structure for a first positive electrode active material. As shown in the figure, the innermost circle schematically represents the core, and from the inside outward are the first coating layer, the second coating layer, and the third coating layer. This figure illustrates an ideal state where each layer is fully coated. In practice, each coating layer can be fully or partially coated.

[0142] In some embodiments, the mass ratio of the first cathode active material to the second cathode active material is 1:7 to 7:1, optionally 1:4 to 4:1, and further optionally 1:3 to 3:1, for example, 1:7, 1:5, 1:3, 1:2, 3:5, 1:1, 5:3, 2:1, 3:1, 5:1, and 7:1. This ensures that the secondary battery has excellent rate performance, excellent cycle performance, and high-temperature stability, high energy density, excellent kinetic performance, and low-temperature performance, reduces interfacial side reactions, and improves the safety of the secondary battery.

[0143] In some embodiments, in the first positive electrode active material, A comprises one or more elements selected from Fe, Ti, V, Ni, Co, and Mg. Selecting the doping element within the above range can enhance the doping effect. This can further reduce the lattice change rate, thereby inhibiting manganese dissolution and reducing electrolyte and active lithium consumption. Furthermore, it can further reduce surface oxygen activity, reducing interfacial side reactions between the first positive electrode active material and the electrolyte, thereby improving the cycle performance and high-temperature storage performance of the secondary battery.

[0144] In some embodiments, in the first positive electrode active material, R includes one element selected from B, Si, N, and S. By selecting the doping element within the above range, the rate performance and conductivity of the secondary battery can be further improved, thereby enhancing the specific capacity, cycle performance, and high-temperature performance of the secondary battery.

[0145] In some embodiments, in the first positive electrode active material, the ratio of y to 1-y is 1:10 to 1:1, and optionally 1:4 to 1:1. Here, y represents the sum of the stoichiometric ratios of the Mn-site doping elements A. When these conditions are met, the energy density, cycle performance, and rate capability of the secondary battery are further improved.

[0146] In some embodiments, in the first positive electrode active material, the ratio of z to 1-z is 1:9 to 1:999, and optionally 1:499 to 1:249. Here, z represents the sum of the stoichiometric ratios of the P-site doping elements R. When these conditions are met, the energy density, cycle performance, and rate capability of the secondary battery are further improved.

[0147] In some embodiments, in the first positive electrode active material, the interplanar spacing of the crystalline pyrophosphate in the first coating layer is in the range of 0.293-0.470 nm, and the angle of the crystal direction (111) is in the range of 18.00°-32.00°; and / or, the interplanar spacing of the crystalline phosphate in the second coating layer is in the range of 0.244-0.425 nm, and the angle of the crystal direction (111) is in the range of 20.00°-37.00°.

[0148] The first coating layer and the second coating layer in the first positive electrode active material of the present application both use crystalline materials. Crystalline pyrophosphate and crystalline phosphate within the above-mentioned interplanar spacing and angle ranges can more effectively suppress the lattice change rate and Mn dissolution of lithium manganese phosphate during lithium insertion and extraction, thereby improving the high-temperature cycle performance, cycle stability and high-temperature storage performance of the secondary battery. The crystalline pyrophosphate and crystalline phosphate in the coating layer can be characterized by conventional technical means in the art, or, for example, by means of a transmission electron microscope (TEM). Under TEM, the core and the coating layer can be distinguished by testing the interplanar spacing.

[0149] The specific test method for the interplanar spacing and angle of the crystalline pyrophosphate and crystalline phosphate in the coating layer may include the following steps:

[0150] Take a certain amount of coated first positive electrode active material sample powder in a test tube, and inject a solvent such as alcohol into the test tube, then stir and disperse it thoroughly, then use a clean disposable plastic pipette to take an appropriate amount of the above solution and drop it on a 300-mesh copper grid. At this time, some powder will remain on the copper grid. Transfer the copper grid and the sample to the TEM sample chamber for testing, obtain the original TEM test image, and save the original image.

[0151] The original image obtained from the above TEM test is opened in the diffractometer software and Fourier transformed to obtain the diffraction pattern. The distance from the diffraction spot to the center position in the diffraction pattern is measured to obtain the interplanar spacing, and the angle is calculated according to the Bragg equation.

[0152] The difference in the interplanar spacing range of crystalline pyrophosphate and the existence of crystalline phosphate can be directly judged by the value of the interplanar spacing.

[0153] In some embodiments, in the first positive electrode active material, the carbon in the third coating layer is a mixture of SP2 carbon and SP3 carbon. Optionally, the molar ratio of SP2 carbon to SP3 carbon is any value in the range of 0.1-10, and can be any value in the range of 2.0-3.0.

[0154] In some embodiments, the molar ratio of sp2 carbon to sp3 carbon can be about 0.1, about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, about 1, about 2, about 3, about 4, about 5, about 6, about 7, about 8, about 9, or about 10, or any range thereof.

[0155] In this application, "about" a numerical value represents a range, which means a range of ±10% of the numerical value.

[0156] By selecting the carbon morphology in the carbon coating, the overall electrical performance of the secondary battery can be improved. Specifically, by using a mixture of SP2 and SP3 carbon and limiting the ratio of SP2 to SP3 carbon to a certain range, the following situations can be avoided: if the carbon in the coating is all amorphous SP3, the conductivity is poor; if it is all graphitized SP2, although the conductivity is good, there are few lithium ion pathways, which is not conducive to lithium insertion and extraction. In addition, limiting the molar ratio of SP2 to SP3 carbon to the above range can achieve good conductivity while ensuring lithium ion pathways, thus facilitating the realization of the secondary battery's functions and its cycle performance.

[0157] The mixing ratio of the SP2 and SP3 carbon morphologies in the third coating layer can be controlled by sintering conditions, such as sintering temperature and sintering time. For example, when using sucrose as the carbon source to prepare the third coating layer, sucrose is cracked at high temperature and then deposited on the second coating layer under high temperature, resulting in a carbon coating layer with both SP3 and SP2 morphologies. The ratio of SP2 carbon morphology to SP3 carbon morphology can be controlled by selecting high-temperature cracking conditions and sintering conditions.

[0158] The structure and characteristics of the third coating layer carbon can be measured by Raman spectroscopy. The specific test method is as follows: by separating the energy spectrum of the Raman test, Id / Ig is obtained (where Id is the peak intensity of SP3 form carbon, and Ig is the peak intensity of SP2 form carbon), thereby confirming the molar ratio of the two.

[0159] In some embodiments, the coating amount of the first coating layer is greater than 0 and less than or equal to 6 weight %, optionally greater than 0 and less than or equal to 5.5 weight %, more optionally greater than 0 and less than or equal to 2 weight %, based on the weight of the kernel; and / or,

[0160] The coating amount of the second coating layer is greater than 0 and less than or equal to 6% by weight, optionally greater than 0 and less than or equal to 5.5% by weight, and more optionally 2-4% by weight, based on the weight of the core; and / or,

[0161] The coating amount of the third coating layer is greater than 0 and less than or equal to 6 wt %, optionally greater than 0 and less than or equal to 5.5 wt %, and more optionally greater than 0 and less than or equal to 2 wt %, based on the weight of the core.

[0162] In this application, the coating amount of each layer is greater than zero.

[0163] In the first positive electrode active material with a core-shell structure of the present application, the coating amount of the three coating layers is preferably within the above range, thereby being able to fully coat the inner core and at the same time further improve the kinetic performance and safety performance of the secondary battery without sacrificing the gram capacity of the positive electrode active material.

[0164] For the first coating layer, by the coating amount being within the above range, the migration of transition metals can be effectively hindered, and the Li + migration, thereby improving the rate performance of the material.

[0165] For the second coating layer, by keeping the coating amount within the above range, the following situations can be reduced: too much coating amount may affect the platform voltage of the entire material; too little coating amount may not achieve sufficient coating effect.

[0166] For the third coating layer, the carbon coating mainly plays the role of enhancing the electron transmission between particles. However, since the structure also contains a large amount of amorphous carbon, the carbon density is relatively low. Therefore, if the coating amount is too large, it will affect the compaction density of the electrode.

[0167] In some embodiments, in the first positive electrode active material, the thickness of the first coating layer is 1-10 nm.

[0168] In some embodiments, the thickness of the first cladding layer can be about 2 nm, about 3 nm, about 4 nm, about 5 nm, about 6 nm, about 7 nm, about 8 nm, about 9 nm, or about 10 nm, or any range thereof.

[0169] In the present application, when the thickness of the first coating layer is in the range of 1-10 nm, it is beneficial to improve the kinetic performance of the battery and can effectively hinder the migration of transition metal ions.

[0170] In some embodiments, in the first positive electrode active material, the second coating layer has a thickness of 2-15 nm.

[0171] In some embodiments, the thickness of the second coating layer may be about 2 nm, about 3 nm, about 4 nm, about 5 nm, about 6 nm, about 7 nm, about 8 nm, about 9 nm, about 10 nm, about 11 nm, about 12 nm, about 13 nm, about 14 nm, about 15 nm, or any range of any of the above values.

[0172] In the present application, when the thickness of the second coating layer is within the range of 2-15 nm, the surface structure of the second coating layer is stable and the side reaction with the electrolyte is small, thus being able to effectively reduce the interface side reaction, thereby improving the high temperature performance of the secondary battery.

[0173] In some embodiments, in the first positive electrode active material, the thickness of the third coating layer is 2-25 nm.

[0174] In some embodiments, the thickness of the third coating layer may be about 2 nm, about 3 nm, about 4 nm, about 5 nm, about 6 nm, about 7 nm, about 8 nm, about 9 nm, about 10 nm, about 11 nm, about 12 nm, about 13 nm, about 14 nm, about 15 nm, about 16 nm, about 17 nm, about 18 nm, about 19 nm, about 20 nm, about 21 nm, about 22 nm, about 23 nm, about 24 nm or about 25 nm, or within any range of any of the above values.

[0175] In the present application, when the thickness of the third coating layer is in the range of 2-25 nm, the electrical conductivity of the material can be improved and the compaction density performance of the battery electrode prepared using the first positive electrode active material can be improved.

[0176] The thickness test of the coating layer is mainly carried out by FIB. The specific method may include the following steps: randomly selecting a single particle from the first positive electrode active material powder to be tested, cutting a thin slice with a thickness of about 100nm from the middle position or near the middle position of the selected particle, and then performing TEM testing on the thin slice to measure the thickness of the coating layer, measuring 3-5 positions, and taking the average value.

[0177] In some embodiments, in the first positive electrode active material, based on the weight of the first positive electrode active material, the manganese content is in the range of 10 wt % to 35 wt %, optionally in the range of 15 wt % to 30 wt %, and more optionally in the range of 17 wt % to 20 wt %.

[0178] In the present application, in the case where manganese is contained only in the core of the first positive electrode active material, the content of manganese may correspond to the content of the core.

[0179] In the first positive electrode active material with a core-shell structure of the present application, the content of manganese element is within the above-mentioned range, which can effectively improve the structural stability and density of the material, thereby improving the cycle, storage and compaction density performance of the secondary battery; and can increase the voltage platform, thereby improving the energy density of the secondary battery.

[0180] In some embodiments, the first positive electrode active material has a phosphorus content in the range of 12 wt % to 25 wt %, and optionally in the range of 15 wt % to 20 wt %, based on the weight of the first positive electrode active material.

[0181] In the first positive electrode active material with a core-shell structure of the present application, the content of phosphorus element is within the above-mentioned range, which can improve the electrical conductivity of the material, and at the same time can improve the stability of the pyrophosphate lattice structure in the inner core, the first coating layer and / or the phosphate in the second coating layer, thereby improving the overall stability of the material.

[0182] In some embodiments, in the first positive electrode active material, based on the weight of the first positive electrode active material, the weight ratio of the manganese element to the phosphorus element ranges from 0.90 to 1.25, and can be optionally from 0.95 to 1.20.

[0183] In the first positive electrode active material with a core-shell structure of the present application, the weight ratio of manganese element to phosphorus element is within the above range, which can effectively inhibit the dissolution of transition metals, improve the stability of the material and the cycle and storage performance of the secondary battery; at the same time, it increases the discharge voltage platform of the material, thereby increasing the energy density of the secondary battery.

[0184] Manganese and phosphorus can be measured using conventional techniques in the art. Specifically, the following method is used to determine the manganese and phosphorus contents: the material is dissolved in dilute hydrochloric acid (concentration 10-30%), the content of each element in the solution is measured using ICP, and then the manganese content is measured and converted to obtain its weight percentage.

[0185] In some embodiments, the lattice change rate of the first positive electrode active material before and after complete lithium deintercalation is less than or equal to 4%, optionally less than or equal to 3.8%, and more optionally 2.0%-3.8%.

[0186] The lithium intercalation and deintercalation process of lithium manganese phosphate (LiMnPO4) is a two-phase reaction. The interfacial stress of the two phases is determined by the lattice change rate before and after lithium intercalation. The smaller the lattice change rate, the smaller the interfacial stress. + Therefore, reducing the lattice change rate of the core will be beneficial to enhance the Li +The first cathode active material having a core-shell structure can achieve a lattice change rate of less than 4% before and after lithium insertion and extraction, thereby improving the rate performance of the secondary battery. The lattice change rate can be measured by methods known in the art, such as X-ray diffraction (XRD).

[0187] In some embodiments, the first positive electrode active material has a Li / Mn antisite defect concentration of less than or equal to 4%, optionally less than or equal to 2.2%, and more optionally between 1.5% and 2.2%.

[0188] In this application, the Li / Mn antisite defect refers to the Li in the LiMnPO4 lattice. + With Mn 2+ The positions of the Li / Mn antisite defects are interchanged. 2+ Li exchange occurs + Occupy + In the present application, the Li / Mn antisite defect concentration can be measured according to JIS K 0131-1996, for example.

[0189] The first cathode active material with a core-shell structure in this application can achieve the above-mentioned low Li / Mn antisite defect concentration. Although the mechanism is not yet clear, the inventors of this application speculate that due to the Li + With Mn 2+ There will be a position swap, and Li + The transmission channel is a one-dimensional channel, so Mn 2+ In Li + It will be difficult to migrate in the channel, thus hindering Li + Therefore, the first cathode active material with a core-shell structure of the present invention has a low concentration of Li / Mn antisite defects within the above range, thus reducing the Mn 2+ Obstacle Li + transmission, while improving the gram capacity and rate performance of the first positive electrode active material.

[0190] In some embodiments, the first cathode active material has a compaction density at 3T of greater than or equal to 2.2 g / cm 3 , can be selected as greater than or equal to 2.2g / cm 3 and less than or equal to 2.8g / cm 3 The higher the compaction density, the greater the weight of the active material per unit volume. Therefore, increasing the compaction density is beneficial to increasing the volumetric energy density of the battery cell. The compaction density can be measured according to GB / T24533-2009.

[0191] In some embodiments, the surface oxygen valence state of the first positive electrode active material is less than or equal to -1.90, and optionally from -1.98 to -1.90.

[0192] The stable valence state of oxygen is -2. The closer the valence state is to -2, the stronger its electron-accepting ability, that is, the stronger its oxidizing property. Under normal circumstances, its surface valence state is below -1.7. By limiting the surface oxygen valence state of the first positive electrode active material to the above range, the present application can reduce the interfacial side reactions between the first positive electrode material and the electrolyte, thereby improving the battery cell's cycling performance, high-temperature storage gas production, and other performance.

[0193] The surface oxygen valence state can be measured by methods known in the art, such as by electron energy loss spectroscopy (EELS).

[0194] In some embodiments, the sum of the mass of the first positive electrode active material and the second positive electrode active material accounts for 88% to 98.7% of the mass of the positive electrode sheet, further ensuring that the secondary battery has excellent rate performance, kinetic performance, cycle performance, and low-temperature performance, and has a high energy density.

[0195] In some embodiments, the average particle size of the primary particles of the first positive electrode active material is in the range of 50-500 nm, and the volume median particle size Dv50 is in the range of 200-300 nm. Since the particles will agglomerate, the actual measured size of the secondary particles after agglomeration may be 500-40000 nm. The size of the first positive electrode active material particles will affect the processing of the material and the compaction density performance of the electrode. By selecting the average particle size of the primary particles to be within the above range, the following situations can be reduced: the average particle size of the primary particles of the first positive electrode active material is small, which may cause particle agglomeration, difficulty in dispersion, and require more binder, resulting in poor brittleness of the electrode; the average particle size of the primary particles of the first positive electrode active material is large, which may cause larger gaps between particles and reduce the compaction density.

[0196] Through the above scheme, the lattice change rate of lithium manganese phosphate and Mn dissolution during the lithium insertion and deinsertion process can be effectively suppressed, thereby improving the high-temperature cycle stability and high-temperature storage performance of the secondary battery.

[0197] In this application, the median particle size Dv50 refers to the particle size corresponding to the cumulative volume distribution percentage of the material reaching 50%. In this application, the median particle size Dv50 of the material can be determined using laser diffraction particle size analysis. For example, it can be determined using a laser particle size analyzer (e.g., Malvern Master Size 3000) in accordance with standard GB / T 19077-2016.

[0198] By controlling the process (for example, fully mixing and grinding the materials of various sources), it is possible to ensure that each element is evenly distributed in the crystal lattice without aggregation. The main characteristic peak positions in the XRD diagram of lithium manganese phosphate doped with elements A and R are consistent with those of undoped LiMnPO4, indicating that no impurity phase is introduced during the doping process. Therefore, the improvement in the core performance is mainly due to element doping, rather than impurity phases. After preparing the first positive electrode active material, the inventors of the present application used a focused ion beam (FIB) to cut out the middle area of ​​the prepared first positive electrode active material particles, and tested them through transmission electron microscopy (TEM) and X-ray energy dispersive spectroscopy (EDS) to find that each element was evenly distributed without aggregation.

[0199] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0200] In some embodiments, the positive electrode film layer may also contain other positive electrode active materials for batteries known in the art. As an example, the positive electrode active material may include at least one of the following materials: an olivine-structured lithium-containing phosphate, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other conventional materials that can be used as battery positive electrode active materials may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, at least one of lithium nickel oxide (such as LiNiO2), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, and their modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0201] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.

[0202] In some embodiments, the positive electrode film layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0203] The method for preparing the first positive electrode active material comprises the following steps:

[0204] Steps for providing core material: The core chemical formula is Li 1+x Mn 1-y A y P 1-z R z O4, wherein x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A is one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and can be one or more elements selected from Fe, Ti, V, Ni, Co and Mg, R is one or more elements selected from B, Si, N and S, and can be one element selected from B, Si, N and S;

[0205] Coating step: provide Li a MP2O7 and / or M b (P2O7) c and X n PO4 suspension, adding the core material to the suspension and mixing, and sintering to obtain the first positive electrode active material, wherein a is selected from any value in the range of 0 to 2, b is selected from any value in the range of 1 to 4, and c is selected from any value in the range of 1 to 6, and the values ​​of a, b and c meet the following conditions: the crystalline pyrophosphate Li a MP2O7 or M b (P2O7) c Maintain electrical neutrality; M is independently one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb or Al; n is greater than 0 and less than or equal to 3; X is one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb or Al;

[0206] The first positive electrode active material has a core-shell structure, which includes a core, a first coating layer covering the core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer, wherein the first coating layer includes crystalline pyrophosphate Li a MP2O7 and / or M b(P2O7) c The second coating layer includes crystalline phosphate X n PO4, the third coating layer is carbon.

[0207] In some embodiments, the step of providing a core material comprises the following steps:

[0208] Step (1): mixing a manganese source, a dopant of element A, and an acid in a container and stirring to obtain manganese salt particles doped with element A;

[0209] Step (2): Mixing the manganese salt particles doped with element A with a lithium source, a phosphorus source and a dopant of element R in a solvent to obtain a slurry, and sintering the slurry under an inert gas atmosphere to obtain a core doped with element A and element R, wherein the core doped with element A and element R is Li 1+x Mn 1-y A y P 1-z R z O4, wherein x is any value in the range of -0.100-0.100, y is any value in the range of 0.001-0.500, z is any value in the range of 0.001-0.100, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and may be selected from the group consisting of Fe, Ti, V, Ni, Co and Mg, and R includes one or more elements selected from the group consisting of B, Si, N and S. Alternatively, R includes one element selected from the group consisting of B, Si, N and S.

[0210] The preparation method of the present application has no particular restrictions on the source of the material. The source of a certain element may include one or more of the element's simple substance, sulfate, halide, nitrate, organic acid salt, oxide or hydroxide. The precursor is the source that can achieve the purpose of the preparation method of the present application.

[0211] In some embodiments, in the step of providing the core material, the dopant of element A includes one or more of the elements Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, each of which is a single substance, carbonate, sulfate, chloride, nitrate, organic acid salt, oxide, and hydroxide.

[0212] In some embodiments, in the step of providing the core material, the dopant of element R includes one or more of inorganic acids, sub-acids, organic acids, sulfates, chlorides, nitrates, organic acid salts, oxides, and hydroxides of one or more elements selected from B, Si, N, and S.

[0213] In some embodiments, in the step of providing the core material, the manganese source can be a manganese-containing substance known in the art that can be used to prepare lithium manganese phosphate. As an example, the manganese source can be one or more selected from elemental manganese, manganese dioxide, manganese phosphate, manganese oxalate, and manganese carbonate.

[0214] In some embodiments, in the step of providing the core material, the acid can be one or more selected from organic acids such as hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, silicic acid, silicic acid, and organic acids such as oxalic acid. In some embodiments, the acid is a dilute organic acid with a concentration of 60% by weight or less.

[0215] In some embodiments, in the step of providing the core material, the lithium source can be a lithium-containing material known in the art that can be used to prepare lithium manganese phosphate. As an example, the lithium source is one or more selected from lithium carbonate, lithium hydroxide, lithium phosphate, and lithium dihydrogen phosphate.

[0216] In some embodiments, in the step of providing the core material, the phosphorus source can be a phosphorus-containing substance known in the art that can be used to prepare lithium manganese phosphate. As an example, the phosphorus source is one or more selected from diammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, and phosphoric acid.

[0217] In some embodiments, in the step of providing the core material, after the manganese source, the dopant of element A and the acid react in a solvent to obtain a manganese salt suspension doped with element A, the suspension is filtered, dried, and sand-milled to obtain manganese salt particles doped with element A having a particle size of 50-200 nm.

[0218] In some embodiments, in the step of providing the core material, the slurry in step (2) is dried to obtain a powder, and then the powder is sintered to obtain a core doped with element A and element R.

[0219] In some embodiments, step (1) is mixed at a temperature of 20-120° C., optionally 40-120° C.; and / or

[0220] In step (1), stirring is performed at 400-700 rpm for 1-9 h, optionally 3-7 h.

[0221] Optionally, the reaction temperature in step (1) can be about 30°C, about 50°C, about 60°C, about 70°C, about 80°C, about 90°C, about 100°C, about 110°C or about 120°C; the stirring in step (1) is carried out for about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours or about 9 hours; optionally, the reaction temperature and stirring time in step (1) can be in any range of the above-mentioned arbitrary values.

[0222] In some embodiments, step (2) is mixed at a temperature of 20-120° C., optionally 40-120° C., for 1-12 hours. Alternatively, the reaction temperature in step (2) can be about 30° C., about 50° C., about 60° C., about 70° C., about 80° C., about 90° C., about 100° C., about 110° C., or about 120° C.; the mixing in step (2) is carried out for about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours, about 10 hours, about 11 hours, or about 12 hours; alternatively, the reaction temperature and mixing time in step (2) can be within any range of the above values.

[0223] When the temperature and time during the preparation of the core particles are within the above ranges, the core obtained and the positive electrode active material prepared therefrom have fewer lattice defects, which is beneficial to inhibiting manganese dissolution and reducing interfacial side reactions between the positive electrode active material and the electrolyte, thereby improving the cycle performance and safety performance of the secondary battery.

[0224] In some embodiments, in the step of providing the core material, during the preparation of the dilute acid manganese particles doped with elements A and R, the pH of the solution is controlled to be 3.5-6, optionally 4-6, and more optionally 4-5. It should be noted that in the present application, the pH of the resulting mixture can be adjusted by methods commonly used in the art, for example, by adding an acid or a base.

[0225] In some embodiments, in step (2), the molar ratio of the manganese salt particles to the lithium source and the phosphorus source is 1:0.5-2.1:0.5-2.1. Optionally, the molar ratio of the manganese salt particles doped with element A to the lithium source and the phosphorus source is about 1:1:1.

[0226] In some embodiments, in the step of providing the core material, the sintering conditions in the process of preparing lithium manganese phosphate doped with A element and R element are: sintering at 600-950°C for 4-10 hours in an inert gas or a mixed atmosphere of inert gas and hydrogen; optionally, the sintering can be at about 650°C, about 700°C, about 750°C, about 800°C, about 850°C or about 900°C for about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours or about 10 hours; optionally, the sintering temperature and sintering time can be within any range of the above-mentioned values. In the process of preparing lithium manganese phosphate doped with elements A and R, if the sintering temperature is too low and the sintering time is too short, the crystallinity of the material core will be low, which will affect the overall performance. When the sintering temperature is too high, impurities will easily appear in the material core, thus affecting the overall performance. When the sintering time is too long, the particles in the material core will grow larger, thus affecting the gram capacity, compaction density and rate performance.

[0227] In some embodiments, in the step of providing the core material, the protective atmosphere is a mixed gas of 70-90 volume % nitrogen and 10-30 volume % hydrogen.

[0228] In some embodiments, the coating step comprises:

[0229] First coating step: dissolving a source of element M, a phosphorus source, an acid, and optionally a lithium source in a solvent to obtain a first coating layer suspension; thoroughly mixing the core obtained in the core step with the first coating layer suspension obtained in the first coating step, drying, and then sintering to obtain a material coated with the first coating layer;

[0230] Second coating step: dissolving the source of element X, the phosphorus source and the acid in a solvent to obtain a second coating layer suspension; fully mixing the first coating layer material obtained in the first coating step with the second coating layer suspension obtained in the second coating step, drying, and then sintering to obtain a material coated with two coating layers;

[0231] The third coating step: dissolving the carbon source in a solvent and fully dissolving it to obtain a third coating layer solution; then adding the material coated with two coating layers obtained in the second coating step to the third coating layer solution, mixing them evenly, drying, and then sintering to obtain a material coated with three coating layers, i.e., the positive electrode active material.

[0232] In some embodiments, in the coating step, the source of the element M includes one or more of the elements Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb or Al, each of which is a single substance, carbonate, sulfate, chloride, nitrate, organic acid salt, oxide, or hydroxide.

[0233] In some embodiments, in the coating step, the source of element X includes one or more of the elements Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, or Al, each of which is a single substance, carbonate, sulfate, chloride, nitrate, organic acid salt, oxide, or hydroxide.

[0234] The amount of each source of elements A, R, M, and X added depends on the target doping amount, and the ratio of the amount of lithium source, manganese source, and phosphorus source used conforms to the stoichiometric ratio.

[0235] As an example, the carbon source includes one or more of starch, sucrose, glucose, polyvinyl alcohol, polyethylene glycol, and citric acid.

[0236] In some embodiments, in the first coating step, the pH of the solution containing the source of element M, the phosphorus source, the acid, and optionally the lithium source is controlled to be 3.5-6.5, and then stirred and reacted for 1-5 hours, and then the solution is heated to 50-120°C and maintained at this temperature for 2-10 hours, and / or sintered at 650-800°C for 2-6 hours.

[0237] In some embodiments, in the first coating step, the reaction is fully carried out. Alternatively, in the first coating step, the reaction is carried out for about 1.5 hours, about 2 hours, about 3 hours, about 4 hours, about 4.5 hours or about 5 hours. Alternatively, in the first coating step, the reaction time of the reaction can be within any range of the above-mentioned arbitrary numerical values.

[0238] In some embodiments, in the first coating step, the pH of the solution is controlled to be 4-6. Alternatively, in the first coating step, the solution is heated to about 55°C, about 60°C, about 70°C, about 80°C, about 90°C, about 100°C, about 110°C, or about 120°C, and maintained at this temperature for about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours, or about 10 hours; alternatively, in the first coating step, the temperature and the holding time may be within any range of the above values.

[0239] In some embodiments, in the first coating step, sintering may be performed at about 650°C, about 700°C, about 750°C, or about 800°C for about 2 hours, about 3 hours, about 4 hours, about 5 hours, or about 6 hours; optionally, the sintering temperature and sintering time may be within any range of the above values.

[0240] In the first coating step, by controlling the sintering temperature and time within the above ranges, the following situations can be avoided: when the sintering temperature in the first coating step is too low and the sintering time is too short, the crystallinity of the first coating layer will be low and the amorphous material will be more, which will lead to a decrease in the effect of inhibiting metal dissolution, thereby affecting the cycle performance and high-temperature storage performance of the secondary battery; when the sintering temperature is too high, impurities will appear in the first coating layer, which will also affect its effect of inhibiting metal dissolution, thereby affecting the cycle and high-temperature storage performance of the secondary battery; when the sintering time is too long, the thickness of the first coating layer will increase, affecting the Li + migration, thereby affecting the material's specific capacity and rate performance.

[0241] In some embodiments, in the second coating step, the source of element X, the phosphorus source, and the acid are dissolved in a solvent, stirred, and reacted for 1-10 hours, and then the solution is heated to 60-150° C. and maintained at this temperature for 2-10 hours, and / or sintered at 500-700° C. for 6-10 hours.

[0242] Alternatively, in the second coating step, the reaction is fully carried out. Alternatively, in the second coating step, the reaction is carried out for about 1.5 hours, about 2 hours, about 3 hours, about 4 hours, about 4.5 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours or about 10 hours. Alternatively, in the second coating step, the reaction time of the reaction can be in any range of the above arbitrary numerical values.

[0243] Optionally, in the second coating step, the solution is heated to about 65°C, about 70°C, about 80°C, about 90°C, about 100°C, about 110°C, about 120°C, about 130°C, about 140°C or about 150°C and maintained at this temperature for about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours or about 10 hours; optionally, in the second coating step, the temperature of heating and the holding time may be within any range of any of the above values.

[0244] In the step of providing the core material and the first coating step and the second coating step, before sintering, that is, in the preparation of the core material where the chemical reaction occurs (steps (1)-(2)) and in the preparation of the first coating layer suspension and the second coating layer suspension, by selecting appropriate reaction temperature and reaction time as above, the following situations can be avoided: when the reaction temperature is too low, the reaction cannot occur or the reaction rate is slow; when the temperature is too high, the product decomposes or forms a mixed phase; when the reaction time is too long, the product particle size is large, which may increase the time and difficulty of subsequent processes; when the reaction time is too short, the reaction is incomplete and the obtained product is small.

[0245] Optionally, in the second coating step, the sintering can be performed at about 550°C, about 600°C or about 700°C for about 6 hours, about 7 hours, about 8 hours, about 9 hours or about 10 hours; optionally, the sintering temperature and sintering time can be within any range of the above-mentioned values.

[0246] In the second coating step, by controlling the sintering temperature and time within the above range, the following situations can be avoided: when the sintering temperature in the second coating step is too low and the sintering time is too short, the second coating layer will have low crystallinity and more amorphous state, which will reduce the performance of the surface reaction activity of the material, thereby affecting the circulation and high-temperature storage performance of the secondary battery; when the sintering temperature is too high, it will cause the second coating layer to have impurities, which will also affect its effect of reducing the surface reaction activity of the material, thereby affecting the circulation and high-temperature storage performance of the secondary battery; when the sintering time is too long, the thickness of the second coating layer will increase, affecting the voltage platform of the material, thereby reducing the energy density of the material, etc.

[0247] In some embodiments, the sintering in the third coating step is performed at 700-800° C. for 6-10 hours. Alternatively, in the third coating step, the sintering can be performed at about 700° C., about 750° C., or about 800° C. for about 6 hours, about 7 hours, about 8 hours, about 9 hours, or about 10 hours. Alternatively, the sintering temperature and sintering time can be within any range of the aforementioned values.

[0248] In the third coating step, by controlling the sintering temperature and time within the above range, the following situations can be avoided: when the sintering temperature in the third coating step is too low, the degree of graphitization of the third coating layer will decrease, affecting its conductivity, thereby affecting the specific capacity of the material; when the sintering temperature is too high, the degree of graphitization of the third coating layer will be too high, affecting the Li + When the sintering time is too short, the coating layer will be too thin, which will affect its conductivity and thus affect the gram capacity of the material; when the sintering time is too long, the coating layer will be too thick, which will affect the compaction density of the material.

[0249] In the above-mentioned first coating step, second coating step and third coating step, drying is carried out at a drying temperature of 100°C to 200°C, optionally 110°C to 190°C, more optionally 120°C to 180°C, even more optionally 120°C to 170°C, most optionally 120°C to 160°C, and the drying time is 3-9h, optionally 4-8h, more optionally 5-7h, and most optionally about 6h.

[0250] The first positive electrode active material prepared by the method for preparing the first positive electrode active material of the present application reduces the dissolution of Mn and Mn-doping elements in secondary batteries after cycling, and exhibits improved high-temperature stability, high-temperature cycling performance, and rate performance. Furthermore, the raw material is widely available, the cost is low, and the process is simple, making it conducive to industrialization.

[0251] [Negative electrode]

[0252] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0253] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0254] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0255] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0256] In some embodiments, the negative electrode film layer may further include a binder. For example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0257] In some embodiments, the negative electrode film layer may further include a conductive agent. For example, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0258] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0259] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0260] [Electrolytes]

[0261] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.

[0262] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.

[0263] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0264] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0265] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.

[0266] [Isolation film]

[0267] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.

[0268] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0269] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.

[0270] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.

[0271] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0272] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG2 shows a secondary battery 5 having a square structure as an example.

[0273] In some embodiments, referring to FIG3 , the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0274] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0275] Figure 4 shows an example battery module 4. Referring to Figure 4 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.

[0276] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0277] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.

[0278] Figures 5 and 6 illustrate an example battery pack 1. Referring to Figures 5 and 6 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be positioned over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0279] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.

[0280] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0281] Figure 7 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.

[0282] [Preparation Example]

[0283] The following describes the preparation examples of the present application. The preparation examples described below are exemplary and are intended only to explain the present application and are not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the preparation examples, the preparations were performed according to the techniques or conditions described in the literature in the art or according to the product specifications. Reagents or instruments used without specifying the manufacturer are all commercially available conventional products.

[0284] The sources of raw materials involved in the preparation examples of this application are as follows:

[0285] Preparation of positive electrode active materials and their slurry

[0286] Preparation Example 1

[0287] Step S1: Preparation of Fe, Co, V and S co-doped manganese oxalate

[0288] 689.6g of manganese carbonate, 455.27g of ferrous carbonate, 4.65g of cobalt sulfate, and 4.87g of vanadium dichloride were added to a mixer and thoroughly mixed for 6 hours. The resulting mixture was then transferred to a reactor, and 5L of deionized water and 1260.6g of oxalic acid dihydrate were added. The mixture was heated to 80°C and stirred at 500 rpm for 6 hours, mixing until the reaction terminated and no bubbles were generated, resulting in a manganese oxalate suspension co-doped with Fe, Co, and V. The suspension was then filtered, dried at 120°C, and sand-milled to obtain manganese oxalate particles with a particle size of 100nm.

[0289] Step S2: Preparation of Li core 0.997 Mn 0.60 Fe 0.393 V 0.004 Co 0.003 P 0.997 S 0.003 O4

[0290] Take 1793.1g of manganese oxalate prepared in (1), 368.3g of lithium carbonate, 1146.6g of ammonium dihydrogen phosphate and 4.9g of dilute sulfuric acid, add them to 20L of deionized water, stir them thoroughly, and evenly mix and react at 80°C for 10h to obtain a slurry. The slurry is transferred to a spray drying equipment for spray drying and granulation, and dried at a temperature of 250°C to obtain a powder. In a protective atmosphere (90% nitrogen and 10% hydrogen), the powder is sintered in a roller kiln at 700°C for 4h to obtain a core material. The element content of the core material is detected by inductively coupled plasma emission spectroscopy (ICP), and the core chemical formula is shown above.

[0291] Step S3: Preparation of the first coating layer suspension

[0292] Preparation of Li2FeP2O7 solution: 7.4 g of lithium carbonate, 11.6 g of ferrous carbonate, 23.0 g of ammonium dihydrogen phosphate and 12.6 g of oxalic acid dihydrate were dissolved in 500 mL of deionized water, the pH was controlled to 5, and then stirred and reacted at room temperature for 2 h to obtain a solution. The solution was then heated to 80°C and maintained at this temperature for 4 h to obtain a first coating layer suspension.

[0293] Step S4: coating of the first coating layer

[0294] 1571.9 g of the doped lithium manganese phosphate core material obtained in step S2 was added to the first coating layer suspension (coating material content of 15.7 g) obtained in step S3, and the mixture was stirred and mixed for 6 h. After mixing evenly, it was transferred to a 120 ° C oven and dried for 6 h, and then sintered at 650 ° C for 6 h to obtain the pyrophosphate-coated material.

[0295] Step S5: Preparation of the second coating layer suspension

[0296] 3.7 g of lithium carbonate, 11.6 g of ferrous carbonate, 11.5 g of ammonium dihydrogen phosphate and 12.6 g of oxalic acid dihydrate were dissolved in 1500 mL of deionized water, and then stirred and reacted for 6 hours to obtain a solution. The solution was then heated to 120° C. and maintained at this temperature for 6 hours to obtain a second coating layer suspension.

[0297] Step S6: coating with the second coating layer

[0298] 1586.8 g of the pyrophosphate-coated material obtained in step S4 was added to the second coating layer suspension (coating material content of 47.1 g) obtained in step S5, and the mixture was stirred and mixed for 6 h. After mixing evenly, it was transferred to a 120°C oven and dried for 6 h, and then sintered at 700°C for 8 h to obtain a two-layer coated material.

[0299] Step S7: Preparation of the third coating layer aqueous solution

[0300] 37.3 g of sucrose was dissolved in 500 g of deionized water, and then stirred and fully dissolved to obtain a sucrose aqueous solution.

[0301] Step S8: coating with the third coating layer

[0302] 1633.9 g of the two-layer coated material obtained in step S6 was added to the sucrose solution obtained in step S7, and stirred and mixed together for 6 hours. After mixing evenly, it was transferred to a 150°C oven for drying for 6 hours, and then sintered at 700°C for 10 hours to obtain a three-layer coated material.

[0303] Preparation Examples 2 to 42 and Comparative Examples 1 to 17

[0304] The positive electrode active materials of Preparation Examples 2 to 42 and Comparative Examples 1 to 17 were prepared in a manner similar to Preparation Example 1. The differences in the preparation of the positive electrode active materials are shown in Tables 1-6.

[0305] Among them, comparative examples 1-2, 4-10 and 12 are not coated with the first layer, and therefore do not have steps S3-S4; comparative example 1-11 is not coated with the second layer, and therefore does not have steps S5-S6.

[0306] Preparation Example 43

[0307] Lithium manganate LiMn2O4 is used as the positive electrode active material.

[0308] Preparation Example 44

[0309] The positive electrode active materials of Preparation Example 1 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0310] Preparation Example 45

[0311] The positive electrode active materials of Preparation Example 2 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0312] Preparation Example 46

[0313] The positive electrode active materials of Preparation Example 3 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0314] Preparation Example 47

[0315] The positive electrode active materials of Preparation Example 4 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0316] Preparation Example 48

[0317] The positive electrode active materials of Preparation Example 5 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0318] Preparation Example 49

[0319] The positive electrode active materials of Preparation Example 6 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0320] Preparation Example 50

[0321] The positive electrode active materials of Preparation Example 7 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0322] Preparation Example 51

[0323] The positive electrode active materials of Preparation Example 8 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0324] Preparation Example 52

[0325] The positive electrode active materials of Preparation Example 9 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0326] Preparation Example 53

[0327] The positive electrode active materials of Preparation Example 10 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0328] Preparation Example 54

[0329] The positive electrode active materials of Preparation Example 11 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0330] Preparation Example 55

[0331] The positive electrode active materials of Preparation Example 12 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0332] Preparation Example 56

[0333] The positive electrode active materials of Preparation Example 13 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0334] Preparation Example 57

[0335] The positive electrode active materials of Preparation Example 14 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0336] Preparation Example 58

[0337] The positive electrode active materials of Preparation Example 15 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0338] Preparation Example 59

[0339] The positive electrode active materials of Preparation Example 16 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0340] Preparation Example 60

[0341] The positive electrode active materials of Preparation Example 17 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0342] Preparation Example 61

[0343] The positive electrode active materials of Preparation Example 18 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0344] Preparation Example 62

[0345] The positive electrode active materials of Preparation Example 19 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0346] Preparation Example 63

[0347] The positive electrode active materials of Preparation Example 20 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0348] Preparation Example 64

[0349] The positive electrode active materials of Preparation Example 21 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0350] Preparation Example 65

[0351] The positive electrode active materials of Preparation Example 22 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0352] Preparation Example 66

[0353] The positive electrode active materials of Preparation Example 23 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0354] Preparation Example 67

[0355] The positive electrode active materials of Preparation Example 24 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0356] Preparation Example 68

[0357] The positive electrode active materials of Preparation Example 25 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0358] Preparation Example 69

[0359] The positive electrode active materials of Preparation Example 26 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0360] Preparation Example 70

[0361] The positive electrode active materials of Preparation Example 27 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0362] Preparation Example 71

[0363] The positive electrode active materials of Preparation Example 28 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0364] Preparation Example 72

[0365] The positive electrode active materials of Preparation Example 29 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0366] Preparation Examples 73 to 85

[0367] The positive electrode active materials of Preparation Examples 73 to 85 were prepared in a manner similar to Preparation Example 1. The differences in the preparation of the positive electrode active materials are shown in Tables 7-8.

[0368] Table 7: Investigation of the first coating layer material (Preparation Examples 73-79)

[0369] Table 8: Investigation of the second coating layer material (Preparation Examples 80-85)

[0370] Comparative Example 18

[0371] The positive electrode active materials of Comparative Example 1 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0372] Comparative Example 19

[0373] The positive electrode active materials of Comparative Example 2 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0374] Comparative Example 20

[0375] The positive electrode active materials of Comparative Example 3 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0376] Comparative Example 21

[0377] The positive electrode active materials of Comparative Example 4 and Preparation Example 43 were mixed in a mass ratio of 1:1.

[0378] Comparative Example 22

[0379] The positive electrode active materials of Comparative Example 5 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0380] Comparative Example 23

[0381] The positive electrode active materials of Comparative Example 6 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0382] Comparative Example 24

[0383] The positive electrode active materials of Comparative Example 7 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0384] Comparative Example 25

[0385] The positive electrode active materials of Comparative Example 8 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0386] Comparative Example 26

[0387] The positive electrode active materials of Comparative Example 9 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0388] Comparative Example 27

[0389] The positive electrode active materials of Comparative Example 10 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0390] Comparative Example 28

[0391] The positive electrode active materials of Comparative Example 12 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0392] Comparative Example 29

[0393] The positive electrode active materials of Comparative Example 13 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0394] Comparative Example 30

[0395] The positive electrode active materials of Comparative Example 14 and Preparation Example 43 were mixed at a mass ratio of 1:1.

[0396] The positive electrode active material prepared above, the conductive agent superconducting carbon black (Super-P), and the binder polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) in a weight ratio of 92:2.5:5.5, and stirred and mixed evenly to obtain a slurry of the positive electrode active material with a solid content of 60% w / w.

[0397] Preparation of positive electrode

[0398] Example 1

[0399] The slurry of the positive electrode active material of Preparation Example 1 was prepared at a temperature of 0.019 g / cm 2 The coating amount is evenly coated on both sides of the current collector aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P1.

[0400] Example 2

[0401] The slurry of the positive electrode active material of Preparation Example 43 was prepared at 0.019 g / cm 2 The coating amount is evenly coated on both sides of the current collector aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P2.

[0402] Example 3

[0403] The slurry of the positive electrode active material of Preparation Example 1 was prepared at a temperature of 0.019 g / cm 2 The coating amount was evenly coated on one side of the aluminum foil, and the slurry of the positive electrode active material of Preparation Example 43 was coated at 0.2 g / cm 2 The coating amount is evenly coated on the other side of the aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P3.

[0404] Example 4

[0405] The slurry of the positive electrode active material of Preparation Example 44 was prepared at 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, and the rest is the same as in Example 3 to obtain the positive electrode sheet P4.

[0406] Example 5

[0407] The slurry of the positive electrode active material of Preparation Example 1 was prepared at a temperature of 0.019 g / cm 2 The coating amount was evenly coated on one side of the aluminum foil, and the slurry of the positive electrode active material of Preparation Example 44 was coated at 0.019 g / cm 2 The coating amount is evenly coated on the other side of the aluminum foil, and the rest is the same as in Example 3 to obtain the positive electrode sheet P5.

[0408] Example 6

[0409] The slurry of the positive electrode active material of Preparation Example 43 was prepared at 0.019 g / cm 2 The coating amount was evenly coated on one side of the aluminum foil, and the slurry of the positive electrode active material of Preparation Example 44 was coated at 0.019 g / cm 2 The coating amount is evenly coated on the other side of the aluminum foil, and the rest is the same as in Example 3 to obtain the positive electrode sheet P6.

[0410] Example 7

[0411] The slurry of the positive electrode active material of Preparation Example 1 and the slurry of the positive electrode active material of Preparation Example 43 were sequentially coated on both sides of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 Then, it was dried in vacuum at a high temperature of 100-120°C for 14 hours and compacted by a roller press to obtain the positive electrode sheet P7.

[0412] Example 8

[0413] The slurry of the positive electrode active material of Preparation Example 43 and the slurry of the positive electrode active material of Preparation Example 1 were sequentially coated on both sides of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 , the rest is the same as in Example 7, and a positive electrode sheet P8 is obtained.

[0414] Example 9

[0415] The slurry of the positive electrode active material of Preparation Example 1 and the slurry of the positive electrode active material of Preparation Example 44 were sequentially coated on both sides of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 , the rest is the same as in Example 7, and the positive electrode sheet P9 is obtained.

[0416] Example 10

[0417] The slurry of the positive electrode active material of Preparation Example 44 and the slurry of the positive electrode active material of Preparation Example 1 were sequentially coated on both sides of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 , the rest is the same as in Example 7, and a positive electrode sheet P10 is obtained.

[0418] Example 11

[0419] The slurry of the positive electrode active material of Preparation Example 43 and the slurry of the positive electrode active material of Preparation Example 44 were sequentially coated on both sides of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 , the rest is the same as in Example 7, and a positive electrode sheet P11 is obtained.

[0420] Example 12

[0421] The slurry of the positive electrode active material of Preparation Example 44 and the slurry of the positive electrode active material of Preparation Example 43 were sequentially coated on both sides of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 , the rest is the same as in Example 7, and a positive electrode sheet P12 is obtained.

[0422] Example 13

[0423] The slurry of the positive electrode active material of Preparation Example 1 and the slurry of the positive electrode active material of Preparation Example 43 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm2 The positive electrode active material slurry of Preparation Example 1 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 Then, it was dried in vacuum at a high temperature of 100-120°C for 14 hours and compacted by a roller press to obtain the positive electrode sheet P13.

[0424] Example 14

[0425] The slurry of the positive electrode active material of Preparation Example 1 and the slurry of the positive electrode active material of Preparation Example 43 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The slurry of the positive electrode active material of Preparation Example 43 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest are the same as in Example 13, and a positive electrode sheet P14 is obtained.

[0426] Example 15

[0427] The slurry of the positive electrode active material of Preparation Example 1 and the slurry of the positive electrode active material of Preparation Example 43 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The slurry of the positive electrode active material of Preparation Example 44 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest are the same as in Example 13, and the positive electrode sheet P15 is obtained.

[0428] Example 16

[0429] The slurry of the positive electrode active material of Preparation Example 43 and the slurry of the positive electrode active material of Preparation Example 1 were sequentially coated on the A side of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 The positive electrode active material slurry of Preparation Example 1 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest are the same as in Example 13, and a positive electrode sheet P16 is obtained.

[0430] Example 17

[0431] The slurry of the positive electrode active material of Preparation Example 43 and the slurry of the positive electrode active material of Preparation Example 1 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The slurry of the positive electrode active material of Preparation Example 43 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest are the same as in Example 13, and a positive electrode sheet P17 is obtained.

[0432] Example 18

[0433] The slurry of the positive electrode active material of Preparation Example 43 and the slurry of the positive electrode active material of Preparation Example 1 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The slurry of the positive electrode active material of Preparation Example 44 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest are the same as in Example 13, and the positive electrode sheet P18 is obtained.

[0434] Example 19

[0435] The slurry of the positive electrode active material of Preparation Example 1 and the slurry of the positive electrode active material of Preparation Example 44 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The positive electrode active material slurry of Preparation Example 1 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest are the same as in Example 13, and the positive electrode sheet P19 is obtained.

[0436] Example 20

[0437] The slurry of the positive electrode active material of Preparation Example 1 and the slurry of the positive electrode active material of Preparation Example 44 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The slurry of the positive electrode active material of Preparation Example 43 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest is the same as in Example 13, and a positive electrode sheet P20 is obtained.

[0438] Example 21

[0439] The slurry of the positive electrode active material of Preparation Example 1 and the slurry of the positive electrode active material of Preparation Example 44 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The slurry of the positive electrode active material of Preparation Example 44 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest is the same as Example 13, and the positive electrode sheet P21 is obtained.

[0440] Example 22

[0441] The positive electrode active material slurry of Preparation Example 44 and the positive electrode active material slurry of Preparation Example 1 were sequentially coated on the A side of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 The positive electrode active material slurry of Preparation Example 1 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest is the same as Example 13, and the positive electrode sheet P22 is obtained.

[0442] Example 23

[0443] The positive electrode active material slurry of Preparation Example 44 and the positive electrode active material slurry of Preparation Example 1 were sequentially coated on the A side of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 The slurry of the positive electrode active material of Preparation Example 43 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest is the same as Example 13, and the positive electrode sheet P23 is obtained.

[0444] Example 24

[0445] The positive electrode active material slurry of Preparation Example 44 and the positive electrode active material slurry of Preparation Example 1 were sequentially coated on the A side of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 The slurry of the positive electrode active material of Preparation Example 44 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest is the same as Example 13, and a positive electrode sheet P24 is obtained.

[0446] Example 25

[0447] The slurry of the positive electrode active material of Preparation Example 43 and the slurry of the positive electrode active material of Preparation Example 44 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The positive electrode active material slurry of Preparation Example 1 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest is the same as Example 13, and the positive electrode sheet P25 is obtained.

[0448] Example 26

[0449] The slurry of the positive electrode active material of Preparation Example 43 and the slurry of the positive electrode active material of Preparation Example 44 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The slurry of the positive electrode active material of Preparation Example 43 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest is the same as Example 13, and the positive electrode sheet P26 is obtained.

[0450] Example 27

[0451] The slurry of the positive electrode active material of Preparation Example 43 and the slurry of the positive electrode active material of Preparation Example 44 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The slurry of the positive electrode active material of Preparation Example 44 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest are the same as in Example 13, and a positive electrode sheet P27 is obtained.

[0452] Example 28

[0453] The slurry of the positive electrode active material of Preparation Example 44 and the slurry of the positive electrode active material of Preparation Example 43 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The positive electrode active material slurry of Preparation Example 1 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest is the same as Example 13, and the positive electrode sheet P28 is obtained.

[0454] Example 29

[0455] The slurry of the positive electrode active material of Preparation Example 44 and the slurry of the positive electrode active material of Preparation Example 43 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The slurry of the positive electrode active material of Preparation Example 43 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest is the same as Example 13, and the positive electrode sheet P29 is obtained.

[0456] Example 30

[0457] The slurry of the positive electrode active material of Preparation Example 44 and the slurry of the positive electrode active material of Preparation Example 43 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The slurry of the positive electrode active material of Preparation Example 44 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest is the same as Example 13, and a positive electrode sheet P30 is obtained.

[0458] Example 31

[0459] The slurry of the positive electrode active material of Preparation Example 45 was prepared at 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P31.

[0460] Example 32

[0461] The slurry of the positive electrode active material of Preparation Example 46 was prepared at 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P32.

[0462] Example 33

[0463] The slurry of the positive electrode active material of Preparation Example 47 was prepared at 0.019 g / cm2 The coating amount is evenly applied on both sides of the current collector aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P33.

[0464] Example 34

[0465] The slurry of the positive electrode active material of Preparation Example 48 was prepared at a temperature of 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P34.

[0466] Example 35

[0467] The slurry of the positive electrode active material of Preparation Example 49 was prepared at a temperature of 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P35.

[0468] Example 36

[0469] The slurry of the positive electrode active material of Preparation Example 50 was prepared at a temperature of 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P36.

[0470] Example 37

[0471] The slurry of the positive electrode active material of Preparation Example 51 was prepared at a temperature of 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, and the rest is the same as in Example 3 to obtain a positive electrode sheet P37.

[0472] Example 38

[0473] The slurry of the positive electrode active material of Preparation Example 52 was prepared at 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, and the rest is the same as in Example 3 to obtain the positive electrode sheet P38.

[0474] Example 39

[0475] The slurry of the positive electrode active material of Preparation Example 53 was prepared at 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, and the rest is the same as in Example 3 to obtain a positive electrode sheet P39.

[0476] Example 40

[0477] The slurry of the positive electrode active material of Preparation Example 54 was prepared at 0.019 g / cm 2The coating amount is evenly applied on both sides of the current collector aluminum foil, and the rest is the same as in Example 3 to obtain a positive electrode sheet P40.

[0478] Example 41

[0479] The slurry of the positive electrode active material of Preparation Example 55 was prepared at a temperature of 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, and the rest is the same as in Example 3 to obtain a positive electrode sheet P41.

[0480] Example 42

[0481] The slurry of the positive electrode active material of Preparation Example 56 was prepared at a temperature of 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, and the rest is the same as in Example 3 to obtain a positive electrode sheet P42.

[0482] Positive electrode sheets P43 to P99 were manufactured according to the method of Example 42, and the different parameters are shown in Table 9.

[0483] Table 9 Parameters of positive electrode “*”: The first layer refers to the layer in contact with the aluminum foil surface, and the second layer refers to the layer disposed on the first layer. “#”: The first positive electrode active material refers to the positive electrode active materials prepared in Preparation Examples 1 to 29, Comparative Examples 1 to 10, and Comparative Examples 12-14.

[0484] Preparation of negative electrode sheet

[0485] The negative electrode active material artificial graphite, the conductive agent superconducting carbon black (Super-P), the binder styrene-butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC-Na) were dissolved in deionized water in a mass ratio of 95%:1.5%:1.8%:1.7%, and after being fully stirred and mixed, a negative electrode slurry with a viscosity of 3000mPa.s and a solid content of 52% was obtained; the negative electrode slurry was coated on a 6μm negative electrode current collector copper foil, and then baked at 100℃ for 4 hours to dry, and roll-pressed to obtain a negative electrode sheet with a compaction density of 1.75g / cm3.

[0486] Isolation film

[0487] Made of polypropylene film.

[0488] Preparation of electrolyte

[0489] Ethylene carbonate, dimethyl carbonate, and 1,2-propylene glycol carbonate were mixed in a volume ratio of 1:1:1, and LiPF6 was uniformly dissolved in the above solution to obtain an electrolyte solution. The concentration of LiPF6 in the electrolyte solution was 1 mol / L.

[0490] Preparation of full batteries

[0491] The above-mentioned positive electrode sheets are wound in the order of negative electrode sheet, separator, and positive electrode sheet to form bare cells. Aluminum and copper tabs are punched out to obtain bare cells. The copper and copper tabs, and the aluminum and aluminum tabs of the two bare cells are welded to the battery top cover through adapters. After the bare cells are wrapped with insulation, they are placed in an aluminum shell. The top cover and the aluminum shell are welded to form a dry cell. The dry cell is baked to remove water, and then an electrolyte is injected. The battery is formed and aged to obtain a complete battery. The battery structure made with positive electrode sheets P1, P2, P3, P8, P10, P11, P12, P17, P18, P23, P24, P26, and P27 is shown in Figures 8-20.

[0492] Preparation of button cells

[0493] The above-mentioned positive electrode sheet, negative electrode and electrolyte are assembled together in a button battery box to form a button battery (hereinafter also referred to as "button battery").

[0494] Ⅰ. Performance Test of Cathode Active Materials

[0495] 1. Lattice change rate test method:

[0496] Under a constant temperature of 25°C, the positive electrode active material sample was placed in an XRD (model: Bruker D8 Discover) and tested at 1° / min. The test data was sorted and analyzed, and the lattice constants a0, b0, c0 and v0 at this time were calculated with reference to the standard PDF card (a0, b0 and c0 represent the lengths of each aspect of the unit cell, and v0 represents the unit cell volume, which can be directly obtained through the XRD refinement results).

[0497] The above-mentioned buckle battery preparation method is used to prepare the positive electrode active material sample into a buckle battery, and the buckle battery is charged at a small rate of 0.05C until the current is reduced to 0.01C. The positive electrode sheet in the buckle battery is then taken out and immersed in dimethyl carbonate (DMC) for 8 hours. It is then dried, powdered, and particles with a particle size of less than 500nm are screened out. Samples are taken and their unit cell volume v1 is calculated in the same way as the above-mentioned test of fresh samples, and (v0-v1) / v0×100% is used as the lattice change rate (unit cell volume change rate) before and after complete deintercalation of lithium.

[0498] 2. Determination of Li / Mn antisite defect concentration:

[0499] The XRD results from the "lattice change rate measurement method" are compared with the PDF (Powder Diffraction File) card of the standard crystal to determine the Li / Mn antisite defect concentration. Specifically, the XRD results from the "lattice change rate measurement method" are imported into the General Structural Analysis System (GSAS) software to automatically obtain a refined result, which includes the site occupancy of different atoms. The Li / Mn antisite defect concentration is then obtained by reading the refined result.

[0500] 3. Determination of compacted density:

[0501] 5g of the prepared positive electrode active material powder was placed in a compaction mold (U.S. CARVER mold, model 13mm). The mold was then placed on a compaction density instrument. A pressure of 3T was applied, and the thickness of the powder under pressure (the thickness after pressure relief) was read on the instrument. The compaction density was calculated using ρ = m / v. The area used was the standard small image area of ​​1540.25mm. 2 .

[0502] 4. Determination of 3C charging constant current ratio:

[0503] Under a constant temperature environment of 25°C, the fresh full batteries prepared in the above preparation examples and comparative examples were allowed to stand for 5 minutes and discharged to 2.5V at 1 / 3C. After standing for 5 minutes, they were charged to 4.3V at 1 / 3C, and then charged at a constant voltage at 4.3V until the current was less than or equal to 0.05mA. After standing for 5 minutes, the charging capacity at this time was recorded as C0. After discharging to 2.5V at 1 / 3C, standing for 5 minutes, and then charging to 4.3V at 3C, standing for 5 minutes, and the charging capacity at this time was recorded as C1. The 3C charging constant current ratio is C1 / C0×100%.

[0504] The higher the 3C charging constant current ratio, the better the rate performance of the secondary battery.

[0505] 5. Transition metal Mn (and Mn-doped Fe) dissolution test:

[0506] After cycling at 45°C until the capacity decayed to 80%, the full batteries made of the positive electrode active materials of the above preparation examples and comparative examples were discharged at a rate of 0.1C to a cut-off voltage of 2.0V. The batteries were then disassembled, the negative electrode sheet was taken out, and 30 unit areas (1540.25mm 2) discs were measured by inductively coupled plasma emission spectroscopy (ICP) using an Agilent ICP-OES730. The amounts of Fe (if Fe is doped at the Mn site of the cathode active material) and Mn were calculated based on the ICP results, thereby estimating the amount of Mn (and Fe doped at the Mn site) released after cycling. This testing was conducted in accordance with EPA-6010D-2014.

[0507] 6. Determination of surface oxygen valence state:

[0508] Take 5g of the above-prepared positive electrode active material sample and prepare it into a buckle battery according to the above-mentioned buckle battery preparation method. The buckle battery is charged at a small rate of 0.05C until the current is reduced to 0.01C. Then take out the positive electrode sheet in the buckle battery and soak it in DMC for 8 hours. Then dry it, scrape the powder, and screen out the particles with a particle size of less than 500nm. The obtained particles are measured by electron energy loss spectroscopy (EELS, the instrument model used is Talos F200S) to obtain the energy loss near-edge structure (ELNES), which reflects the state density and energy level distribution of the element. According to the state density and energy level distribution, the number of occupied electrons is calculated by integrating the valence band state density data, thereby inferring the valence state of the surface oxygen after charging.

[0509] 7. Measurement of manganese and phosphorus in positive electrode active materials:

[0510] 5 g of the above-prepared positive electrode active material was dissolved in 100 ml of reverse aqua regia (concentrated hydrochloric acid: concentrated nitric acid = 1:3) (concentrated hydrochloric acid concentration ~37%, concentrated nitric acid concentration ~65%), and the content of each element in the solution was tested by ICP. The content of manganese or phosphorus was then measured and converted (the amount of manganese or phosphorus / the amount of positive electrode active material * 100%) to obtain its weight proportion.

[0511] 8. Method for measuring initial gram capacity of button batteries:

[0512] At 2.5-4.3 V, the button batteries prepared in the above preparation examples and comparative examples were charged to 4.3 V at 0.1 C, then charged at a constant voltage at 4.3 V to a current less than or equal to 0.05 mA, allowed to stand for 5 minutes, and then discharged to 2.0 V at 0.1 C. The discharge capacity at this time was the initial gram capacity, recorded as D0.

[0513] 9. Full battery cell expansion test at 60°C for 30 days:

[0514] The full batteries prepared in the above-mentioned preparation examples and comparative examples were stored at 100% state of charge (SOC) at 60°C. The open circuit voltage (OCV) and AC internal resistance (IMP) of the battery cells were measured before, during and after storage to monitor the SOC, and the volume of the battery cells was measured. The full battery was taken out after every 48 hours of storage, and the open circuit voltage (OCV) and internal resistance (IMP) were tested after standing for 1 hour, and the volume of the battery cells was measured by the drainage method after cooling to room temperature. The drainage method is to first measure the gravity F1 of the battery cell separately using a balance that automatically converts the unit data on the dial, and then completely place the battery cell in deionized water (density is known to be 1g / cm 3 ), measure the gravity F2 of the battery cell at this time, and the buoyancy F 浮 That is F1-F2, and then according to Archimedes principle F 浮 =ρ×g×V 排 , the cell volume V = (F1-F2) / (ρ×g) is calculated.

[0515] According to the OCV and IMP test results, the batteries of all embodiments maintained an SOC of more than 99% throughout the experiment until the end of storage.

[0516] After 30 days of storage, the cell volume was measured, and the percentage increase in the cell volume after storage relative to the cell volume before storage was calculated.

[0517] 10. Full battery cycle performance test at 45°C:

[0518] At a constant temperature of 45°C, charge the battery at 2.5-4.3V at 1C to 4.3V, then charge it at a constant voltage at 4.3V until the current is ≤0.05mA, let it stand for 5 minutes, and then discharge it at 1C to 2.5V. The capacity is recorded as D n (n=0, 1, 2, ...) Repeat the above process until the capacity fades to 80%. Record the number of repetitions at this point, which is the number of cycles corresponding to 80% capacity retention at 45°C.

[0519] 11. Crystal plane spacing and angle test:

[0520] Take 1g of each positive electrode active material powder prepared above into a 50mL test tube, and inject 10mL of 75% alcohol by mass into the test tube, then stir and disperse it thoroughly for 30 minutes, then use a clean disposable plastic pipette to take an appropriate amount of the above solution and drop it on a 300-mesh copper grid. At this time, some powder will remain on the copper grid. Transfer the copper grid and the sample to the TEM (Talos F200s G2) sample chamber for testing, obtain the original TEM test image, and save the original image format (xx.dm3).

[0521] The original image obtained from the above TEM test was opened in DigitalMicrograph software and Fourier transformed (automatically completed by the software after clicking the operation) to obtain the diffraction pattern. The distance from the diffraction spot to the center position in the diffraction pattern was measured to obtain the interplanar spacing, and the angle was calculated according to the Bragg equation.

[0522] By comparing the obtained interplanar spacing and corresponding angle data with their standard values, the materials and crystal states of different coating layers can be identified.

[0523] 12. Coating thickness test:

[0524] The thickness of the coating layer is mainly tested by cutting a thin slice of about 100 nm thick from the middle of a single particle of the positive electrode active material prepared above by FIB, and then performing TEM testing on the thin slice to obtain the original TEM test image and save the original image format (xx.dm3).

[0525] The original image obtained from the above TEM test was opened in DigitalMicrograph software. The coating layer was identified based on the lattice spacing and angle information, and the thickness of the coating layer was measured.

[0526] The thickness of the selected particles was measured at three locations and the average value was taken.

[0527] 13. Determination of the molar ratio of SP2 to SP3 in the third coating carbon layer:

[0528] This test is performed using Raman spectroscopy. By separating the peaks of the Raman spectrum, Id / Ig is obtained, where Id is the peak intensity of the sp3 carbon and Ig is the peak intensity of the sp2 carbon, thereby confirming the molar ratio of the two.

[0529] 14. Determination of the chemical formula of the core and the composition of different coating layers:

[0530] The internal microstructure and surface structure of the positive electrode active material were characterized with high spatial resolution using spherical aberration electron microscopy (ACSTEM), and the core chemical formula of the positive electrode active material and the composition of different coating layers were obtained by combining three-dimensional reconstruction technology.

[0531] The performance test results of the positive electrode active materials of the preparation examples and comparative examples are shown in the table below.

[0532] IV. Battery Test

[0533] The secondary batteries prepared using the positive electrode sheets P1-P99 were tested as follows:

[0534] (1) Determine the energy density and furnace temperature test results of secondary batteries according to the method in the national standard GB 38031-2020 "Safety Requirements for Power Batteries for Electric Vehicles";

[0535] (2) Needle penetration test: Charge the secondary battery to 100% SOC, pierce the battery cell with a Φ8mm steel needle at a speed of 25mm / 2, and observe for 1 hour. If no fire occurs, the test has passed;

[0536] (3) According to the national standard GBT31486-2015 “Electrical performance requirements and test methods for power batteries for electric vehicles”, the room temperature 1C rate charge capacity retention rate (Vs0.33C) and the 0.33C low temperature (-20°C) discharge capacity retention rate of the secondary battery were measured to obtain the battery cell dynamic performance data;

[0537] (4) Determine the cycle life data of secondary batteries in accordance with the national standard GBT31484-2015 “Cycle life requirements and test methods for power batteries for electric vehicles”;

[0538] The above results are shown in Table 16.

[0539] Table 16 Results of battery test

[0540] According to the above results, we can know that:

[0541] Compared with the secondary battery using the positive electrode sheet P1, the secondary battery using the positive electrode sheet P3-P30 has higher energy density, higher room temperature rate charging capacity retention rate, and higher low temperature discharge capacity retention rate. In addition, the secondary battery using the positive electrode sheet P3-P30 successfully passed the furnace temperature test and the needle puncture test; the secondary battery using the positive electrode sheet P3-P30 has a longer cycle life than the secondary battery using the positive electrode sheet P2.

[0542] Compared with batteries using positive electrode sheets P59-P86 containing only the first positive electrode material, batteries using positive electrode sheets P31-P58 containing the first positive electrode active material and the second positive electrode active material have higher room temperature rate charge capacity retention rate and low temperature discharge capacity retention rate; batteries using positive electrode sheets P31-P58 have longer cycle life than batteries using positive electrode sheet P2.

[0543] The above description shows that the secondary battery made of the positive electrode sheet of the present application has higher energy density, higher rate performance, better dynamic performance and low temperature performance, longer cycle life and higher safety.

[0544] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode sheet, comprising a first positive electrode active material and a second positive electrode active material; The first positive electrode active material includes a core, a first coating layer covering the core, a second coating layer covering the first coating layer, and a third coating layer covering the second coating layer; the core contains a compound Li 1+x Mn 1-y A y P 1-z R z O4, the first coating layer comprises crystalline pyrophosphate Li a MP2O7 and / or M b (P2O7) c The second coating layer comprises crystalline phosphate X n PO4, the third coating layer comprises carbon; in, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge; The R includes one or more elements selected from B, Si, N and S; The x is any value in the range of -0.100 to 0.100; The y is any value in the range of 0.001 to 0.500; The z is any value in the range of 0.001 to 0.100; The crystalline pyrophosphate Li a MP2O7 and M b (P2O7) c The M's each independently include one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al, The a is any value in the range of 0 to 2; b is any value in the range of 1 to 4; The c is any value in the range of 1 to 6; The X includes one or more elements selected from the group consisting of Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al; The n is greater than 0 and less than or equal to 3; The second positive electrode active material includes lithium manganese oxide.

2. The positive electrode sheet according to claim 1, wherein: The second positive electrode active material includes LiMn2O4.

3. The positive electrode plate according to claim 1 or 2, comprising a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector; the positive electrode film layer has a single-layer structure or a multi-layer structure; at least one of the positive electrode film layers with a single-layer structure simultaneously comprises the first positive electrode active material and the second positive electrode active material, and / or at least one layer of at least one of the positive electrode film layers with a multi-layer structure simultaneously comprises the first positive electrode active material and the second positive electrode active material.

4. The positive electrode sheet according to claim 1 or 2, comprising a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector; at least one of the positive electrode film layers has a multi-layer structure, and at least one of the multi-layer positive electrode film layers comprises the first positive electrode active material and the second positive electrode active material in different layers respectively; Optionally, at least one of the positive electrode film layers having a multi-layer structure comprises the first positive electrode active material and the second positive electrode active material in adjacent layers respectively.

5. The positive electrode sheet according to claim 1 or 2 comprises a positive electrode current collector and a positive electrode film layer A and a positive electrode film layer B respectively arranged on the two surfaces of the positive electrode current collector; the positive electrode film layer A and the positive electrode film layer B each independently have a single-layer structure or a multi-layer structure; at least one layer of the positive electrode film layer A comprises the first positive electrode active material, and at the same time, at least one layer of the positive electrode film layer B comprises the second positive electrode active material.

6. The positive electrode sheet according to any one of claims 1 to 5, wherein: The mass ratio of the first positive electrode active material to the second positive electrode active material is 1:7 to 7:1, and can be 1:4 to 4:

1.

7. The positive electrode sheet according to any one of claims 1 to 6, wherein: In the first positive electrode active material, The A includes one or more elements of Fe, Ti, V, Ni, Co and Mg, and / or, The R includes one element selected from B, Si, N and S, and / or, The ratio of y to 1-y is 1:10 to 1:1, and can be 1:4 to 1:1, and / or, The ratio of z to 1-z is 1:9 to 1:999, and can be optionally 1:499 to 1:

249.

8. The positive electrode sheet according to any one of claims 1 to 7, wherein: In the first positive electrode active material, the interplanar spacing of the crystalline pyrophosphate in the first coating layer is in the range of 0.293-0.470 nm, and the angle of the crystal direction (111) is in the range of 18.00°-32.00°; and / or, the interplanar spacing of the crystalline phosphate in the second coating layer is in the range of 0.244-0.425 nm, and the angle of the crystal direction (111) is in the range of 20.00°-37.00°.

9. The positive electrode sheet according to any one of claims 1 to 8, wherein: In the first positive electrode active material, the carbon in the third coating layer is a mixture of SP2 carbon and SP3 carbon. Optionally, the molar ratio of the SP2 carbon to the SP3 carbon is any value in the range of 0.1-10, and can be any value in the range of 2.0-3.

0.

10. The positive electrode sheet according to any one of claims 1 to 9, wherein: In the first positive electrode active material, The coating amount of the first coating layer is greater than 0 and less than or equal to 6% by weight, optionally greater than 0 and less than or equal to 5.5% by weight, and more optionally greater than 0 and less than or equal to 2% by weight, based on the weight of the core; and / or, The coating amount of the second coating layer is greater than 0 and less than or equal to 6% by weight, optionally greater than 0 and less than or equal to 5.5% by weight, and more optionally 2-4% by weight, based on the weight of the core; and / or, The coating amount of the third coating layer is greater than 0 and less than or equal to 6% by weight, optionally greater than 0 and less than or equal to 5.5% by weight, and more optionally greater than 0 and less than or equal to 2% by weight, based on the weight of the core.

11. The positive electrode sheet according to any one of claims 1 to 10, wherein: In the first positive electrode active material, The thickness of the first coating layer is 1-10 nm; and / or, The thickness of the second coating layer is 2-15 nm; and / or, The thickness of the third coating layer is 2-25 nm.

12. The positive electrode sheet according to any one of claims 1 to 11, wherein: In the first positive electrode active material, based on the weight of the first positive electrode active material, The manganese content is in the range of 10 wt% to 35 wt%, optionally in the range of 15 wt% to 30 wt%, and more preferably in the range of 17 wt% to 20 wt%; and / or, The phosphorus content is in the range of 12 wt% to 25 wt%, and can be optionally in the range of 15 wt% to 20 wt%; and / or, The weight ratio of manganese element to phosphorus element is 0.90-1.25, and can be optionally 0.95-1.

20.

13. The positive electrode sheet according to any one of claims 1 to 12, wherein: The lattice change rate of the first positive electrode active material before and after complete lithium deintercalation is less than or equal to 4%, optionally less than or equal to 3.8%, and more optionally 2.0%-3.8%.

14. The positive electrode sheet according to any one of claims 1 to 13, wherein: The Li / Mn antisite defect concentration of the first positive electrode active material is less than or equal to 4%, optionally less than or equal to 2.2%, and more optionally 1.5%-2.2%.

15. The positive electrode sheet according to any one of claims 1 to 14, wherein: The compaction density of the first positive electrode active material at 3T is greater than or equal to 2.2 g / cm 3 , can be selected as greater than or equal to 2.2g / cm 3 And less than or equal to 2.8g / cm 3 .

16. The positive electrode sheet according to any one of claims 1 to 15, wherein: The surface oxygen valence state of the first positive electrode active material is less than or equal to -1.90, and can be optionally -1.98 to -1.

90.

17. The positive electrode sheet according to any one of claims 1 to 16, wherein: The sum of the mass of the first positive electrode active material and the second positive electrode active material accounts for 88% to 98.7% of the mass of the positive electrode sheet.

18. A battery comprising the positive electrode sheet according to any one of claims 1 to 17.

19. An electrical device comprising the battery according to claim 18.

Citation Information

Patent Citations

  • Mixed positive electrode material and application thereof

    CN104134815A

  • Positive electrode material, preparation method thereof, battery positive electrode, and lithium ion battery

    CN110098383A

  • Lithium manganese iron phosphate composite material, preparation method thereof and lithium ion battery

    CN114256448A

  • Positive electrode active material and preparation method thereof, positive electrode plate, secondary battery, battery module, battery pack and electric device

    CN116830302A